Isolation and identification of three antagonistic strains against kiwifruit soft rot, study on antibacterial mechanism, and preparation of composite biocontrol agents - Zhengfeng Liu; Longfei Wang; Zhangyang Wang; Li Yao; Fen Zhang; Xueyan Ren; Qingjun Kong (Food Microbiology, 2027)

Biosynthesis and characterization of polyhydroxyalkanoates by next-generation industrial biotechnology using lignocellulosic carbohydrates and VFAs as co-substrates - Qian Chen; Yutian Zhang; Xiaojun Ma; Fen Yin; Yingying Zheng; Dongna Li; Jianing Li (Biomass and Bioenergy, 2026)

Chemical constituents of Paratinospora sagittata and their chemotaxonomic significance - Wei Nie; Zhang-Juan Li; Ye-Ting Shi; Ming Hu; Xing-De Wu; Lin-Fen Ding (Biochemical Systematics and Ecology, 2026)

Prediction of chemoresistance in ovarian cancer based on deep learning with pathological images - Leyan Niu; Xiang Li; Zhiquan Mao; Fen Fu; Mingjie Wang; Hengbin Zhang; Le Chen; Qing Zhang; Xiaoli Tang; Weiming Lou (Functional & Integrative Genomics, 2026)

Identification of novel biomarkers and therapeutic targets for type II ketosis in dairy cows through metabolomics and snRNA-Seq - Xue Feng; Qi Feng; Shuang Liu; Lingkai Zhang; Sayed Haidar Abbas Raza; Bei Cai; Yanfen Ma; Fen Li; Yun Ma (Functional & Integrative Genomics, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Over-expression of the solute carrier gene SLC23A1 as a novel mechanism contributing to imidacloprid resistance in Nilaparvata lugens - Fan Zhang; Zhi-Tao Yu; Yan-Chao Zhang; Yu-Qiu Xie; Li-Xiang Wang; Cong-Fen Gao (Insect Biochemistry and Molecular Biology, 2026)

Phocaeicola vulgatus alleviates obesity through cross-species arginine production and hepatic retinoic acid signaling - Yushi Li; Jinmei Li; Jiteng Deng; Pei Xia; Guicheng Zhou; Zhenjun Zhu; Yu Ding; Jingge Yang; Fen Zhang (Food Research International, 2026)

Characterization and modification of chickpea husk dietary fibers: Potential applications in gummy candy and emulsion-based food products - Xiangyu Liu; Yifan Zhang; Liang Wang; Minwei Zhang; Fen Li; Huiling Yan; Kaiwen Wu; Feng Zhang; Qiao Zhang; Jun Liu; Chunlan Zhang; Liling Wang; et al. (Food Hydrocolloids, 2026)

Hierarchical tubular carbon with differentiated Co/N/P functional units for selective silver recovery via capacitive electrosorption-reduction coupling - Linyi Ren; Yongping He; Fen Li; Lei Zhang; Ao Qiu; Xiayu Li; Xinhua Huang (Desalination, 2026)

Single-channel magnetotactile interface with structurally decoupled polarity–eigenfrequency encoding for in-plane sliding-direction decoding - Xiaojuan Hou; Shaowei Quan; Xin Zhang; Huipeng Zhao; Lin Shi; Fen Li; Wenping Geng; Jian He; Xiujian Chou (Chemical Engineering Journal, 2026)

A competitive binding strategy to fabricate silk fibroin/PANI hydrogels for integrated self-powered flexible supercapacitors and strain sensors - Chengzhao Liu; Yuanhang Luo; Xinyi Zhang; Fen Zhu; Yulan Liu; Huabo Huang; Xianghua Yu; Jiayou Ji; Liang Li (Chemical Engineering Journal, 2026)

A facile and scalable strategy to construct superhydrophilic PET membranes for ultrahigh-flux oil–water separation - Quanbing Shen; Beibei Yu; Dong Chen; Fen Zhang; Li Wang; Yuhong Ma; Wantai Yang (Chemical Engineering Journal, 2026)

Rapid screening method of glucocorticoid residues in sample-limited cell-cultured meat - Peiwen Yu; Simeng Li; Chen Zhang; Xiaohui Li; Hongping Wang; Fen Jin (Food Research International, 2026)

Carboxylate-driven interfacial regulation via polyacrylic acid additive for stable magnesium metal batteries - Bo Li; Hui Miao; Jiu-Xi Dong; Meng-Qi Zhu; Song-Lin Li; Cheng-Bao Liu; Fen Zhang; Shuo-Qi Li; Lan-Yue Cui (Chemical Engineering Journal, 2026)

Tracing microplastics uptake and translocation in plants using aggregation-induced emission materials - Yang Liu; Siqi Yang; Xia Wang; Wei Du; Nan Fu; Penglin Li; Heng Wei; Fen Zhao; Zijie Qiu; Hao Qiu; Yanxu Zhang; Willie J.G.M. Peijnenburg; et al. (Journal of Hazardous Materials, 2026)

Multidimensional analysis of pathogen epidemic patterns, their correlation with milk quality, and drug resistance and virulence traits of dominant pathogenic Escherichia coli in high-somatic-cell buffalo milk: Guangxi, China - Yifei Xiang; Zhifei Wei; Xuelian Mo; Yuying Liao; Chongli Wen; Mengyao Liao; Jiazhou Wei; Changhua Lin; Wenjing Li; Jiaji Chen; Lei Xu; Min Zhu; et al. (Food Microbiology, 2026)

Corrigendum to “Neomycin-sensitive gut bacteria-derived brassicasterol mediates the anti-obesity effects of Cordyceps militaris polysaccharide” [Food Res. Int. 230 (2026) 118574] - Jie Cai; Aohuan Huang; Linghui You; Zelin Wang; Chaoyang Huang; Rong Huang; Ying Li; Tingting Liang; Fen Zhang; Qingping Wu; Juan Wang; Zhenjun Zhu; et al. (Food Research International, 2026)

Wholly-Tröger's base with strong rigidity-based polyamide loose nanofiltration membranes with excellent permeance, precise dye/salt selectivity, and durability under strongly acidic conditions - Nian Zhang; Jing-Feng Chen; Chen Peng; Dong Yu; Chen-Jie Wei; Li-Fen Liu (Desalination, 2026)

Short-term hot spring balneotherapy ameliorates sleep disorders: wrist-worn wearable-assessed sleep improvement associated with neuroimmune, tryptophan metabolic and gut microbiome alterations - Xiao Zhang; Yue Zou; Xiao-qin He; Yi-hang Xu; Hong-xia Li; Fen Yang; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Si-fan Hao; Meng-meng Wang; et al. (International Journal of Biometeorology, 2026)

Crotiglianoids A−M, tigliane-type diterpenoids from the seeds of Croton tiglium and their anti-hepatic fibrosis activity - Guang-Hai Zhu; Zhen-Zhou Han; Rong Huang; Li-Fen Ma; Xin-Yi Hu; Fei-Yu Zhang; Yi-Ling Liao; Lu Gan; De-an Guo; Wei Li (Phytochemistry, 2026)

Corrigendum to “Inhibition expansion mechanism of compound eluent during ammonium removal from weathered crust elution-deposited rare earth tailings” [Miner. Eng. 235 (2026) 109813] - Xiaoju Li; Junxia Yu; Peng hui Zhang; Xue fen Liu; Yun Wu; Zhenyue Zhang; Xiaodi Li; Chunqiao Xiao; Ruan Chi (Minerals Engineering, 2026)

Characterization of gluten quality of single-locus wheat lines with double null alleles at the Glu-1 locus - Shoufen Dai; Lingling Liang; Xiaorong Deng; Sisi Dong; Na Zhang; Chunmei He; Shiqi Luo; Jihao Chen; Fen Lu; Yapeng Li; Zixuan Fan; Bo Lu; et al. (Cereal Research Communications, 2026)

Chemistry-informed marine copper water quality criteria derived via salinity- and DOC-corrected toxicity modeling - Heng Zhang; Qing-Wei Li; Xin-Ming Pu; Jin-Fen Pan; De-chi Lu (Regional Studies in Marine Science, 2026)

Ship hydrodynamic optimization for minimum resistance through an improved grey wolf algorithm and ship model experimental verification - Jie Liu; Li-fen Hu; Bao-ji Zhang; Yong-yi Jiang; Jun-ying Bi; Ying-kai Dong; Guo-hua Yan (Ocean Engineering, 2026)

Ecotoxicity of silver nanoparticles in marine waters: Global gap between exposure and seawater quality criteria - Qing-Wei Li; Heng Zhang; Xin-Ming Pu; Daosen Liu; Jin Li; Romana Manzoor; Jin-Fen Pan (Marine Environmental Research, 2026)

Microplastics enter strawberry fruit tissues directly through the epidermis - Chen Zhang; Simeng Li; Hongping Wang; Xiaohui Li; Lihui An; Fen Jin (Journal of Hazardous Materials, 2026)

Synergistically enhanced mechanical properties, wave-transparency, and low dielectric properties of cyanate ester resins by furfuryl-based diglycidyl-containing hollow polymer microspheres with nanoconfinement effects - Quanbing Shen; Beibei Yu; Dong Chen; Fen Zhang; Li Wang; Yuhong Ma; Wantai Yang (Chemical Engineering Journal, 2026)

Heart injury-induced Fibronectin 1 confers liver dysfunction in zebrafish through hepatic Pparβ signaling - Hongbo Lv; Qi Li; Peng Gao; Yanmei Liu; Xiamisiya Tuniyazi; Fen Du; Hong Yu; Ruilin Zhang (Marine Life Science & Technology, 2026)

Phosphorus Speciation and Mobility in the Dredged Sediment of an Urban Lake: The Role of Coupled Fe-S-P Dynamics and Microbial Succession - Baoquan Li; Min Zhang; Jicheng Zhong; Jiayu Qin; Haiyuan Cai; Chuanzhe Sun; Fanyan Yang; Yanjun Wu; Shanshan Liu; Hui Yang; Fen Huang (Water Research, 2026)

Integrated catalytic production and separation of 5-hydroxymethylfurfural from fructose using resin-based solid acid and hyper-cross-linked adsorption resin in aqueous media - Hairong Chen; Xuefang Chen; Haifeng Chen; Tessafa Abrham Ashagrie; Bo Chen; Fen Peng; Hairong Zhang; Zhili Li; Xinde Chen (Journal of Environmental Chemical Engineering, 2026)

ECCAS: An interactive web platform for assessing water-sustainable ecosystem productivity in large-scale dryland restoration - Ning Chen; Fen Gou; Weibin Zhang; Xinyao Xu; Nan Gao; Shuai Li; Bojie Fu; Yihe Lü; Shuai Wang; Jianwu Yan; Wei Liang (Journal of Environmental Management, 2026)

Unconventional seasonal variation and mechanisms of sediment phosphorus release in an Urban lake - Baoquan Li; Suisui Zhang; Yanjun Wu; Ying Li; Min Zhang; Chuanzhe Sun; Fanyan Yang; Yuyi Wang; Shanshan Liu; Hui Yang; Fen Huang; Jicheng Zhong (Journal of Environmental Sciences, 2026)

Neomycin-sensitive gut bacteria-derived brassicasterol mediates the anti-obesity effects of Cordyceps militaris polysaccharide - Jie Cai; Aohuan Huang; Linghui You; Zelin Wang; Chaoyang Huang; Rong Huang; Ying li; Tingting Liang; Fen Zhang; Qingping Wu; Juan Wang; Zhenjun Zhu; et al. (Food Research International, 2026)

Front-face synchronous fluorescence spectroscopy coupled with PLSR for rapid quantitative analysis of Chinese five-spice powder composition - Fei-Yue Chen; Li-Fen Zhang; Hong-Yan Pan; Xia Huang; Pei Yi; Zhi Jin; Peng-Hui Zhu; Jin Tan (Food Research International, 2026)

Cell type-specific contribution of low-density lipoprotein receptor to atherosclerosis - Wei-Hui Li; Yu-Liang Zhang; Ya-Fen Zhang; Zhenyang Yu; Liang Chen; Hao-Yu Fang; Liang Cheng; Bao-Liang Song; Jie Luo (Science China Life Sciences, 2026)

Warming offsets phosphorus-driven increases in periphyton omega-3 fatty acids - Bowei Zhou; Zhenmin Yang; Fen Guo; Jiaqi You; Martin J. Kainz; Feilong Li; Yuan Zhang (Aquatic Sciences, 2026)

Sensitivity Analysis of a SAR Model for Microseismic Monitoring in the Three Gorges Reservoir Area - Xiao-tong Shen; Li-fen Zhang; Jing-gang Li; Yan-nan Zhao; Sheng-qi Dai; Jing-xuan Huang (Applied Geophysics, 2026)

Low doses of chlorothalonil cause testicular impairment in mammals through the antimicrobial-like mechanism - Han-Zhang Wang; Yi-Ming Xiong; Shi-Lin Song; Qian-Cheng Zhao; Xuan-Yue Chen; Jing-Ran Gao; Yuan-Yuan Li; Zhan-Fen Qin (Journal of Hazardous Materials, 2026)

Highly efficient detoxification of aflatoxin B1 in peanut meals by attapulgite-supported laccase - Fen Tang; Fei Ma; Du Wang; Mengxue Fang; Liangxiao Zhang; Peiwu Li; Li Yu (Food Control, 2026)

Cycloastragenol reduces inflammation and apoptosis in acute lung injury by inhibiting the NF-κB p65 and Akt pathways - Huixian Cheng; Qixiang Xu; Cuifeng Zhang; Liangbin Cao; Fen Yao; Lihui Chen; Min Guo; Sixu Chen; Jiayin Wang; Xiaodong Wang; Qian Li; Yongquan Chen; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Rethinking trophic transfer efficiency in freshwater ecosystems: Current understanding and knowledge gaps - Hua Song; Fen Guo; David Dudgeon; Xiaoguang Ouyang; Feilong Li; Siyong Wu; Zhenmin Yang; Wei Gao; Yuan Zhang; Stuart E. Bunn (Limnology and Oceanography, 2026)
Trophic transfer efficiency (TTE) represents the proportion of energy transferred between consecutive trophic levels within a food web. Though it is a fundamental property that shapes energy flow across all ecosystem types, a comprehensive understanding of TTE in freshwater ecosystems is still lacking. This review evaluated common estimation methods, identified key influencing factors, and outlined future research priorities based on a global freshwater TTE dataset. Methods to estimate TTE include production estimates, carbon‐transfer measurements, model‐based approaches, and predator–prey mass‐ratio estimates; mixed‐effects analyses indicate that method choice significantly structures reported TTE, yet each method has limitations in accuracy and consistency. Trophic transfer efficiency also varies across ecosystem types, consistent with systematic differences in the environmental and biological controls on energy transfer among systems. Light, nutrients, and organic matter affect TTE by altering the abundance and composition of primary producers, whereas food quality, temperature, and dissolved oxygen impact TTE by modulating consumer growth and metabolism of individual consumers. At the community and ecosystem levels, predation pressure, competition, species richness, the presence of non‐native species, and cross‐ecosystem interactions shape community structure, thus affecting TTE. Better understanding of TTE in freshwater ecosystems will depend on refined estimation methods and integration of new techniques, such as remote sensing and stable‐isotope labeling, to improve TTE estimates. Research priorities include understanding the synergistic effects of anthropogenic pressures and climate change on TTE, investigating how food quality and individual‐level metabolic processes govern TTE, and examining the influence of cross‐ecosystem energy fluxes on TTE dynamics. It is essential to recognize that TTE varies among trophic levels and cannot be represented by a single value along the entire food chain. Our synthesis reveals that more research is needed in the tropics and the southern hemisphere to expand our understanding of global variability in TTE. This would facilitate greater use of TTE as an indicator of ecological change or the restoration of efficient energy transfer through freshwater food webs.

Two new abietane diterpenoids from Salvia cavaleriei var. simplicifolia - Qian Wu; Jie Yang; Mi-Na Yang; Li-Jia Ye; Hong-Fen Jiang; Miao Zhang; Xin Wang; Yi-Nan Yang; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2026)

Phragmalin-type limonoid orthoesters from the twigs and leaves of Khaya ivorensis and their cytotoxic activities - Zong-Yi Zhang; Jia-Nan Wang; Peng Sun; Xiao-Cui Shi; Yi-Dian Xiao; Kai-Long Ji; Chun-Fen Xiao; Xiao-Nian Li; You-Kai Xu; Dong-Hua Cao (Phytochemistry, 2026)

NaCl and light quality reprogram carbohydrate metabolism to modulate growth, quality, and flavor in mustard (Brassica juncea) sprouts - Hongmei Di; Ling Li; Liping Su; Lisha Peng; Ling Rao; Zhifeng Chen; Victor Hugo Escalona; Jing Yang; Yu'nong Zhou; Yong Li; Xuena Yu; Kehao Liang; et al. (Food Chemistry, 2026)

Tree-ring based spring sunshine duration reconstruction since AD 1875 in the Nanling Mountains, southeastern China - Wenhuo Liu; Yuxia Huo; Jinbao Li; Fen Zhang; Meixue Yang; Xiaohua Gou (Dendrochronologia, 2026)

Screening vertical-oriented carriers for microalgal biofilms: Interfacial thermodynamics and adaptive secretion of extracellular polymeric substances - Manhuan Zhou; Pingzhong Feng; Fen Liu; Shunni Zhu; Xuming Zhang; Lei Qin; Wei Qi; Wei Liu; Liwen Luo; Zhongming Wang; Xuan Li (Chemical Engineering Journal, 2026)

Correction to: Morphology-based genetic diversity analysis reveals introgressive hybridizations obscure species boundaries of three wild roses endemic to Taiwan Island - Cheng Zhang; Shi-Qi Li; Liang-Ying Li; Xin-Fen Gao (Horticulture, Environment, and Biotechnology, 2026)

Inhibition expansion mechanism of compound eluent during ammonium removal from weathered crust elution-deposited rare earth tailings - Xiaoju Li; Junxia Yu; Peng hui Zhang; Xue fen Liu; Yun Wu; Zhenyue Zhang; Xiaodi Li; Chunqiao Xiao; Ruan Chi (Minerals Engineering, 2026)

Seismic local event slopes estimation using cycle generative adversarial network based on perceptual loss and self attention mechanism - Chao Li; Chenghan Zhang; Xiaotao Wen; Xingye Liu; Fen Lyu; Shaohuan Zu (Journal of Applied Geophysics, 2026)

Motor Cortex VIP Interneurons Participate in Dexmedetomidine-Associated Sleep Modulation - Wei Wang; Hanmei Zhang; Tianqi Zhang; Qianyi Huang; Jiaxin Li; Nuo Li; Yue Xi; Xiaohan Yang; Fen Wang; Jun Tu; Dongmei Ji; Juan Cheng (Molecular Neurobiology, 2026)

miR‑16‑5p Protects RGCs Against Retinal Ischemia–Reperfusion Injury by Modulating Astrocyte-Mediated Neuroinflammation Through the Wip1/NF-κB Signaling Axis - Wen Hu; Wenjing He; Guangyi Huang; Yuchen Zhou; Yue Li; Shuya Tao; Daizai Lei; Fen Tang; Ningning Tang; Li Jiang; Qiangqiang Lan; Hui Huang; et al. (Molecular Neurobiology, 2026)

Oxymatrine Alleviates Cerebral Ischemia/Reperfusion Injury By Targeting HDAC1 to Regulate Mitochondria-Related Autophagy and Oxidative Stress - Chang-Sheng Ma; Bo Han; Yu-Xi Liu; Chang-Ku Shi; Dong-Lun Li; Jin-Fen Guo; Min Bai; Shu-Chen Meng; Li-Ying Zhang; Meng-Yuan Duan; Mao-Tao He (Molecular Neurobiology, 2026)
Oxymatrine (OMT), a major alkaloid extracted from Sophora flavescens, has been widely recognized for its anti-inflammatory and anti-cancer properties. However, its precise neuroprotective mechanisms in cerebral ischemia/reperfusion (I/R) injury remain to be fully elucidated. In this study, we combined in vivo and in vitro models to investigate the therapeutic effects of OMT on cerebral I/R injury and glutamate-induced neuronal toxicity during the reperfusion process. In vivo, a mouse middle cerebral artery occlusion (MCAO) model was established to recapitulate I/R injury, whereas glutamate-exposed HT22 hippocampal neurons were utilized as an in vitro model to mimic excitotoxic damage. Bioinformatics analysis, integrated with molecular docking, identified histone deacetylase 1 (HDAC1) as a potential direct target of OMT. Subsequent experimental validation demonstrated that OMT attenuates I/R-induced brain damage by modulating HDAC1-mediated pathways involved in autophagy and oxidative stress regulation. OMT treatment significantly reduced infarct volume and improved neurological function in mice. At the cellular level, OMT suppressed mitochondrial apoptosis and reactive oxygen species (ROS) accumulation, restored mitochondrial membrane integrity, and rebalanced mitochondrial dynamics by downregulating fission-related proteins (Fis1) and upregulating fusion markers (Mfn2). Additionally, OMT inhibited excessive autophagy through modulation of the PINK1/Parkin signaling pathway, as evidenced by decreased expression of LC3-II/I ratio, PINK1, Parkin, and NBR1, along with restored levels of P62.These findings suggest that OMT exerts its neuroprotective effects in cerebral I/R injury by targeting HDAC1, thereby alleviating oxidative stress and excessive autophagy. This study provides new mechanistic insights and supports OMT as a promising therapeutic candidate for ischemic stroke treatment. Graphical Abstract

Adaptive obstacle avoidance algorithm for wave gliders in dynamic marine environments based on improved DAPF with multi-model prediction - Hongqiang Sang; Wuqiang Li; Shuai Zhang; Xiujun Sun; Fen Liu (Ocean Engineering, 2025)

Hydroxylamine enhanced Fe(Ⅱ)-activated peracetic acid process to promote short-chain fatty acid production during sludge anaerobic fermentation - Jing Zhang; Yanping Zhang; Junliang Dong; Fen Li; Zhenjie Guo; Yibing Li (Journal of Environmental Chemical Engineering, 2025)

Three-dimensional molecular engineering of fluorene-based self-assembled monolayers for high-performance inverted perovskite solar cells - Fen Xia; Xiaohan Lin; Jing Zhang; Jun Yin; Jing Li; Xijiao Mu; Song Tu; Binghui Wu; Nanfeng Zheng (Chemical Engineering Journal, 2025)

Palmitoylation modulates antitumor immunity - Feng Tang; Jia-Long Xu; Qing Zhang; Xi Chen; Ze-Fen Wang; Ya-Di Xu; Zhi-Qiang Li (Molecular Biology Reports, 2025)

Association between legume consumption and risk of esophageal cancer among Chinese adults: a 17-year prospective cohort study - Fengyi Huang; Xiaorui Zhang; Jiayue Li; Xinqing Li; Ru Chen; Shaoming Wang; Fen Liu; Wenqiang Wei (Cancer Causes & Control, 2025)

Projections of Autumn Precipitation Extremes in Southwest China Based on a Statistically Downscaled CMIP6 Dataset - Linxiao Wei; Hongyu Tang; Yong Wang; Yao Wu; Tianyu Zhang; Qilin Li; Jie Zhou; Fen Zhang; Wanhong Li; Tan’anbang Lyu (Journal of Meteorological Research, 2025)

Sediment amplifies organic matter cycling and nutrients feedback in eutrophic lake zones - Junfeng Xing; Yuping Zhou; Ding He; Fen Guo; Penghui Li; Yuan Zhang; Rui Lv; Runze Xue; Changqing Liu; Yihua Xiao (Water Research, 2025)

Corrigendum to “Susceptibility, resistance risk and sublethal effect to fenmezoditiaz, a novel mesoionic insecticide, in the brown planthopper, Nilaparvata lugens” [ Pesticide Biochemistry and Physiology 213 (2025) 106540] - Yan-Chao Zhang; Xiao-Yan Song; Yu Li; Zi-Xin Zhuang; Wen-Nan Ye; Zhao-Yu Liu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2025)

A single N-rich covalent organic framework-based sensor for electrochemical sensing of 2,4,6-trichlorophenol - Wei-Long Shan; Qian Lu; Heng-Ye Li; Zhong-Xia Wang; Rui Zhang; Mei-Jie Wei; Fen-Ying Kong; Wei Wang (Food Chemistry, 2025)

Development of a certified reference material for accurate quantification of patulin in clear apple juice - Qiaoyan Zhang; Fen Dai; Xiaofeng Zhang; Ke Li; Jiaojiao Xu; Zuoyi Zhu; Qiang Wang (Food Chemistry, 2025)

A novel high selectivity, strong acid resistance and antifouling polyamide thin film composite nanofiltration membrane fabricated with 3,3′-diamine-Tröger's base - Liu-Yang Gong; Nian Zhang; Jun-Yan Yu; Yan-Nan Wu; Chen-Jie Wei; He-Lin Zhu; Xue-Li Cao; Li-Fen Liu (Desalination, 2025)

Unveiling the roles of CMPs based 1,3,5-triethynylbenzene for efficient aflatoxins capture: An experimental, theoretical and applicable study - Fei Ma; Fen Tang; Yajie He; Zhaowei Zhang; Peiwu Li; Li Yu (Chemical Engineering Journal, 2025)

Expression of LGALS3 and XPNPEP2 genes and their association with growth traits in sheep - Guoxing Jia; Weimin Wang; Huibing Tian; Xiaojuan Wang; Yukun Zhang; Yuan Zhao; Lijuan He; Zongwu Ma; Xioabing Yang; Dan Xu; Kunchao Han; Peiliang Cao; et al. (Tropical Animal Health and Production, 2025)

Assessing Spatiotemporal Characteristics, Health Impacts and Related Economic Losses of PM2.5, PM10 and O3 in Beijing-Tianjin-Hebei Region from 2015 to 2020 - Ran Gao; Qin Li; Yanping Zhang; Fei Che; Xiaorui Zhang; Yijie Wang; Yijun Zhang; Xite Zheng; Quanmei Li; Fengyi Huang; Chuning Luo; Wanqi Liu; et al. (Environment, Development and Sustainability, 2025)

Current status and influencing factors of blue carbon in seagrass beds: An extensive survey and comprehensive analysis in the Yellow and Bohai Seas, China - Xiang Zhao; Jie Sun; Fan Li; Shao-Wen Li; Hai-Xia Su; Xiu-Fen Ma; Lei Yang; Gui-Xiang Zheng; Wan-Long Sun; Pei-Dong Zhang (Journal of Environmental Management, 2025)

Synergistic engineering of four-pointed star-like layered stacking and oxygen vacancies toward high-efficiency Bi2O2-xSe photocatalysts for the degradation of tetracycline and Congo red - Yao Yang Liu; Zhong Li; Yi Liang; Jing Hao Zhuang; Wen Ji Zhang; Tao Tang; Yin Fen Cheng; Rui Ou; Bao Yue Zhang; Jian Zhen Ou (Journal of Environmental Chemical Engineering, 2025)

MOF-derived TiO2 nanosheets loaded with Nb2O5 for enhanced catalytic hydrogenation of MgH2 - Zhicheng Yang; Weiqi Sun; Yiting Bu; Ruoyang Zhang; Zexuan Yang; Bin Li; Lixian Sun; Fen Xu; Ting Yu; Wenwei Guo; Yi Liu; Zhengyi Liang (Chemical Engineering Journal, 2025)

Nitrogen-oxygen radical generator-mediated in situ activation of live-cell prodrug for rational combination therapy - Ting Hou; Zi-Tao Shen; Wan-Ting Chen; Yang Song; Yin-Yu Yan; Zi-Jiang Luo; You-Yang Li; Yu-Ting Shan; Rui-Cheng Li; Tian-Yu Shen; Jia-Qin Long; Li Yin; et al. (Chemical Engineering Journal, 2025)

The role of N6-methyladenosine (m6A) modification in plants - Cui-Xian Qin; Ao-Mei Li; Zhong-Liang Chen; Fen Liao; Miao Wang; You-Qiang Pan; Li Zhou; Bao-Qing Zhang; Jian-Hui Zhou; Dong-Liang Huang (Theoretical and Applied Genetics, 2025)

Carbon and nitrogen footprints of rice in China: implications for low-carbon rice consumption - Jingyu Zhang; Yingchun Li; Shifeng Li; Fen Ma; Guojun Cao; Guohui Chen; Yanfang Chen; Chunfeng Peng (Nutrient Cycling in Agroecosystems, 2025)

First total synthesis of (±)-sanggenon F and its osteogenic differentiation promoting activity on human mesenchymal stem cells - Ren-Fen Ma; Yue Jing; Hui Song; Bin Wang; Jian Li; Xiu-Shan Yin; Hua Zhang (Natural Product Research, 2025)

Effect of Dandelion Root Extract on Growth, Biochemical Indices, Antioxidant Capacity, Intestinal Histomorphology and Microbiota in Micropterus salmoides - Peng-Ao Liu; Hong-Ling Yang; Jian Huang; Fen Li; Ke-Yun Huang; Zi-Xin Liu; Guo-He Cai; Yun-Zhang Sun (Fishes, 2025)
Intensive aquaculture systems face challenges including compromised immune function and hepatointestinal damage in cultured species. Therefore, it is urgent to seek effective feed additives to strengthen health and immunity in intensive aquaculture. This study evaluated the potential of dandelion root extract (DRE) for improving growth performance, immune response, and hepatointestinal health in juvenile largemouth bass (Micropterus salmoides). Fish were fed diets supplemented with 0.05% (DRE1), 0.1% (DRE2), and 0.15% (DRE3) DRE for 42 days. The results showed that DRE supplementation had no significant effect on growth performance indicators (p > 0.05). However, compared to the control group, the DRE2 and DRE3 groups exhibited significantly reduced AST and ALT activities (p

Anti-inflammatory and antinociceptive effects, toxicity, and phytochemical analysis of Beaumontia grandiflora Wall. - Rui Yang; Dan Teng; Ming-rui Yang; Yi-huan Li; Jian-fen Xiao; Qian-ru Zhang; Hong-ping He; Hua-yi Jiang (Natural Product Research, 2025)

Susceptibility, resistance risk and sublethal effect to fenmezoditiaz, a novel mesoionic insecticide, in the brown planthopper, Nilaparvata lugens - Yan-Chao Zhang; Xiao-Yan Song; Yu Li; Zi-Xin Zhuang; Wen-Nan Ye; Zhao-Yu Liu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2025)

Saleucanes A-J, structurally diverse neo-clerodane diterpenoids from Salvia leucantha with anti-neuroinflammatory activity via TLR4/MYD88/NF-κB pathway - Fen-Cong Pan; Han-Fei Liu; Xiao-Die Shu; Xiao-Qiao Yang; Hua-Yong Lou; Wei-Dong Pan; Ni Zhang; Jin-Yu Li (Phytochemistry, 2025)

Integrating morphology, ecology, and genomics: Unraveling the population genetic and evolution within the Rosa graciliflora complex - Jia Miao; Liang-Ying Li; Zhen-Long Liang; Yu Feng; Cheng Zhang; Shi-Qi Li; Heng-Ning Deng; Jian Ru; Zhong-Yu Tang; Xin-Fen Gao (Molecular Phylogenetics and Evolution, 2025)

In-situ stabilization of conjugated microporous polymer on sieve plates for multifunctional applications: Detection and removal of aflatoxins - Fei Ma; Yajie He; Fen Tang; Lina Fu; Liangxiao Zhang; Peiwu Li; Li Yu (Journal of Hazardous Materials, 2025)

Dissolved organic matter-mediated metabolic shifts in Chlorella sorokiniana enhanced bioremediation of multi-ionic stress - Ting-Bin Hao; Zhong-Hong Zhang; Lan-Lan Hu; Si-Fen Liu; Jin-Hua Mou; Peizeng Yang; Zhiguo Yuan; Qi Zhang; Srinivasan Balamurugan; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; et al. (Journal of Hazardous Materials, 2025)

Recent progress in two-dimensional materials: From emerging structures and synthesis approaches to electronic and sensing applications - Jing Hao Zhuang; Zhong Li; Yi Liang; Tao Tang; Xin Yi Hu; Rui Ou; Qi Jie Ma; Bao Yue Zhang; Yin Fen Cheng; Wen Lin Feng; Jian Zhen Ou (Chemical Engineering Journal, 2025)

Evolution mechanism of catalytic performance in piezo-photocatalytic recycled pervious concrete during hydration to carbonation - Hailiang Fei; Guanyu Liu; Jiayu Wu; Jiaxu Zhang; Yulong Zheng; Mingtao Run; Fen Li; Sanqiang Yang (Chemical Engineering Journal, 2025)

Novel furfuryl-based phosphaphenanthrene containing N/P flame retardant: towards epoxy resin with excellent flame retardancy, enhanced toughness and low dielectric constant - Quanbing Shen; Beibei Yu; Dong Chen; Fen Zhang; Li Wang; Yuhong Ma; Wantai Yang (Chemical Engineering Journal, 2025)

The revolutionizing osteosarcoma therapy of carbon monoxide and doxorubicin synergy via mesoporous silica nanoparticles - Yating Lian; Junyi Zhou; Wei Li; Zhijie Yuan; Minghui Zhong; Tian Wei; Huishan Liang; Shicong Yang; Li Ding; Li-Ming Zhang; Fen Wang (Chemical Engineering Journal, 2025)

Karyotype and evolution trend analysis of seven diploid accessions and their autotetraploid lines of Tartary buckwheat native to China - Li-kun Lian; Pei Zhang; Xiao-fen Wu; Yi-zhong Zhang; Qing-fu Chen (Genetic Resources and Crop Evolution, 2025)

Quantitative assessment of trophic flow based on polyunsaturated fatty acids reveals that high‐quality algae support aquatic food webs irrespective of dams - Juan Huang; Fen Guo; Martin J. Kainz; Stuart E. Bunn; Xiaoguang Ouyang; Feilong Li; Qingping Du; Yuan Zhang (Limnology and Oceanography, 2025)
High‐quality, yet less abundant, food sources sustain river food webs. However, the impacts of dams on these sources and their nutritional contributions to aquatic animals are not well understood. A substantial knowledge gap exists in understanding the quantitative contribution of basal food sources, such as periphyton, to aquatic animal diets and their role in supporting aquatic animals. This study fills this gap by using long‐chain polyunsaturated fatty acids as biomarkers to quantify the dietary contributions of periphyton, submerged leaves, and macrophytes to macroinvertebrates and fish in dammed rivers. Our results showed that periphyton contributed more to the lipid diets of macroinvertebrates and fish than submerged leaves and macrophytes, regardless of dams, and was a high‐quality food source supporting aquatic food webs. The dietary contribution of periphyton to macroinvertebrates decreased at the downstream sites of small dams compared to the upstream sites, while the contribution of leaves and macrophytes increased due to dam‐induced changes in periphyton nutritional quality. The nutritional quality of periphyton correlated positively with its contribution to invertebrate grazers and filterers, while its contribution to fish varied depending on the feeding strategies of fish species. Our findings underscore periphyton as a high‐quality dietary source in dammed river ecosystems and suggest that improving its nutritional quality enhances its contribution to the lipid diets of macroinvertebrates and fish.

Baicalin reduced vandetanib induced myocardial injury by regulating redox balance and NLRP3 inflammasome pathway - Fen Wang; Jianwei Li; Zhixuan Zhang; Guangyi Huang; Xiaodong Zhang; Qian Liu; Wang Xiao; Fengqi Liu; Jialong Sun; Yankui Liu; Yiyi Ma; Ruijuan Zhuang; et al. (Tissue and Cell, 2025)

Study on enhanced heavy metal immobilisation in medical waste incineration bottom ash using calcium carbide residue with nanowire-like calcium carbonate regulation - Mei Yang; Qi Wang; Ning Fen; Xiongxiong Zhang; Wenxin Ji; Yonggang Sun; Yuanyuan Li; Yulong Ma (Journal of Environmental Chemical Engineering, 2025)

Bellidifolin, a constituent from edible Mongolic Liver Tea (Swertia diluta), promotes lipid metabolism by regulating intestinal microbiota and bile acid metabolism in mice during high fat diet-induced obesity - Aikebaier Jumai; Shaohua Chen; Yaodan Wu; Fen Liu; Bailin Li; Baojun Zhu; Liyun Zhao; Kanglun Liu; Qingzhong Zhang; Sheng-Xiang Qiu (Food Bioscience, 2025)

Acute toxicity, bioconcentration, and metabolomic profiling of agrochemical organosilicone spray adjuvants in Zebrafish - Tianyou Feng; Jianling Liu; Ling Wu; Yuanqiang Luo; Ling Liu; Fen Li; Guangbin Wu; Ping Lu; Yuping Zhang (Aquatic Toxicology, 2025)

Anti-ferroptosis effects of undescribed abietane diterpenoids from Prunella vulgaris subsp . hispida (Benth.) Hultén - Heng-Li Yan; Xiao-Qiao Yang; Han-Fei Liu; Fen-Cong Pan; Jin-Yu Li; Wei-Dong Pan; Ni Zhang; Hua-Yong Lou; Chao Sun (Natural Product Research, 2025)

Experimental and numerical study on the hydrodynamic characteristics of a cube fish cage integrated into a wind turbine jacket foundation - Yuan-Mao Zhang; Fen-Fang Zhao; Liu-Yi Huang; Huan-Ran Li; Chun-Wei Bi (Ocean Engineering, 2025)

Dissipation patterns of trisiloxane ethoxylates in cucumber plants and field soils: Insights from different end-capping groups - Simeng Li; Xiaohui Li; Chen Zhang; Bowen Li; Peiwen Yu; Qin Dai; Hongping Wang; Fen Jin (Journal of Hazardous Materials, 2025)

Colloids fractionation and characterization of arsenic (As) and dissolved organic matter (DOM) in surface water around a closed arsenic mine - Zhenzhen Yu; Chaoyang Wei; Fen Yang; Zhiying Li; Bin Jiang; Weijie Dai; Changyuan Tang; Yizhang Zhang (Journal of Hazardous Materials, 2025)

High performance Ni-MgO (111) nanosheet catalysts for CO2 reforming with methane - Xirui Yan; Rui Wang; Fen Yue; Ruicong Wang; Huigang Zhang; Jun Li; Wencai Peng; Jinli Zhang (Fuel, 2025)

Association between sleep quality and serum biomarkers among long-term hot spring bathers: a cross-sectional study - Fen Yang; Yue Zou; Ying-ying Zhang; Hong-xia Li; Yi-hang Xu; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Yuan Yuan; Yun Zhou; Da-yong Zeng; et al. (International Journal of Biometeorology, 2025)

Study on Ground Motion Attenuation Relations for Tectonic and Induced Earthquakes in Western Hubei Region, China - Guang-qin Tong; Li-fen Zhang; Jun Geng; Wei-bing Qin; Yan-nan Zhao; Jing-gang Li (Applied Geophysics, 2025)

Monitoring the insecticide susceptibility of a newly introduced invasive species, Tuta absoluta (Meyrick), in China - Yi-bo Zhang; Han Li; Peng Han; Xiao-cao Tian; Hao Wang; Li-li Geng; Jie Zhang; Wan-xue Liu; Fang-hao Wan; Raul-Narciso Guedes; Desneux Nicolas; Gui-fen Zhang (Crop Protection, 2025)

The regulatory mechanism controlling nitrification inhibitors-induced mitigation of nitrification and NO3−-N leaching in alkaline purple soil - Fabo Liu; Prakash Lakshmanan; Wenxin Zou; Ming Lang; Zhao Lei Li; Fen Zhang; Tao Liang; Jing Chen; Yan Wang; Xiaozhong Wang; Xinping Chen (Journal of Environmental Management, 2025)

Analysis of factors influencing microseismic detection and location in shale gas extraction areas of western Hubei - Wan-peng Hao; Li-fen Zhang; Yan-nan Zhao; Rong-ying Zheng; Wei-bing Qin; Jing-gang Li (Applied Geophysics, 2025)

Global occurrence, food web transfer, and human health risks of polycyclic aromatic hydrocarbons in biota - Jingqian Xie; Ruo Lan; Li Zhang; Jun Yu; Xinran Liu; Zhiyang You; Fen Yang; Tian Lin (Science of The Total Environment, 2025)

Large-scale ecological infrastructures enhance the productivity of agro-socio-ecological systems by reducing soil erosion in the Loess Plateau - Fen Gou; Wei Liang; Yan Liu; Bojie Fu; Zhenguo Wang; Weibin Zhang; Zhigang Chen; Jianwu Yan; Junyi Li; Yihe Lv (Journal of Environmental Management, 2025)

Post-modification of covalent organic framework functionalized aminated carbon nanotubes with active site (Fe) for the sensitive detection of luteolin - Ze-Qi Wei; Wei-Long Shan; Lei Li; Heng-Ye Li; Rui Zhang; Juan-Juan Gao; Zhong-Xia Wang; Fen-Ying Kong; Mei-Jie Wei; Wei Wang (Food Chemistry, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Species-specific sensitivity to CuO nanoparticles: Establishing seawater quality criteria for Chinese marine ecosystems - De-chi Lu; Qing-Wei Li; Xin-Ming Pu; Heng Zhang; Lei Huang; Zhenguang Yan; Jin-Fen Pan (Science of The Total Environment, 2024)

Soil eDNA biomonitoring reveals changes in multitrophic biodiversity and ecological health of agroecosystems - Kaihang Xing; Weijun Lu; Qiqi Huang; Jingze Wu; Heping Shang; Qian Wang; Fen Guo; Qingping Du; Zhonglong Yin; Yuan Zhang; Feilong Li (Environmental Research, 2024)

Efficiency and mechanism of sludge thickening by a novel sandwich-like forward osmosis composite membrane constructed on microporous polyethylene separator - Fen Chen; Jingyuan Yu; Jintai Hu; Guoqing Zhang; Chunhui Du; Xuchun Li (Chemical Engineering Journal, 2024)

Morphology-based genetic diversity analysis reveals introgressive hybridizations obscure species boundaries of three wild roses endemic to Taiwan Island - Cheng Zhang; Shi-Qi Li; Liang-Ying Li; Xin-Fen Gao (Horticulture, Environment, and Biotechnology, 2024)

Distribution, bioaccumulation and human exposure risk of bisphenol analogues, bisphenol A diglycidyl ether and its derivatives in the Dongjiang River basin, south China - Danlin Yang; Daoming Zhao; Honglin Chen; Yanpeng Cai; Yuxian Liu; Fen Guo; Feilong Li; Yuan Zhang; Zhihao Xu; Jingchuan Xue; Kurunthachalam Kannan (Science of The Total Environment, 2024)

Salinity influence correction for zinc ion seawater quality criteria and ecological risk assessment in Chinese seas - Jia-yin Xu; Heng Zhang; Xin-Ming Pu; Qing-wei Li; Jin-Fen Pan; Zhen-Guang Yan (Science of The Total Environment, 2024)

Area-wide survey and monitoring of insecticide resistance in the brown planthopper, Nilaparvata lugens (Stål), from 2020 to 2023 in China - Wen-Nan Ye; Yu Li; Yan-Chao Zhang; Zhao-Yu Liu; Xin-Yu Song; Xin-Guo Pei; Shun-Fan Wu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2024)

Intensifying the selective sulfidation of nickel in saprolitic laterites by sodium salts - Chen Li; Wei Liu; Fen Jiao; Tianfu Zhang; Junwei Han; Wenqing Qin (Minerals Engineering, 2024)

Two ethylene-responsive transcription factors, AdVAL2 and AdKAN2, regulate early steps in kiwifruit starch degradation - Yang Tong; Wen-yue Su; Yu-tong Chen; Xiao-fen Liu; Qiu-yun Zhang; Tong-hui Qi; Andrew C. Allan; Xiang Li; Xue-ren Yin (Postharvest Biology and Technology, 2024)

The toxicity of cisplatin derives from effects on renal organic ion transporters expression and serum endogenous substance levels - Mingkang Zhang; Yile Li; Yanrong Ma; Yongwen Jin; Xueyan Gou; Yufan Yuan; Fen Xu; Xin'an Wu (Food and Chemical Toxicology, 2024)

Future changes in extremes across China based on NEX-GDDP-CMIP6 models - Yang Baogang; Wei Linxiao; Tang Hongyu; Li Yonghua; Wang Yong; Zhang Fen; Zhou Jie; Zhang Tianyu; Lv Tananbang (Climate Dynamics, 2024)

Rutin alleviates Pb-induced oxidative stress, inflammation and cell death via activating Nrf2/ARE system in SH-SY5Y cells - Fen Li; Lin Zhang; Xingxu Zhang; Qimeng Fang; Yingshun Xu; Hui Wang (NeuroToxicology, 2024)

Improve flotation efficiency of refractory tungsten ore and reduce carbon emission in flotation process: A case study of Sandaozhuang deposit in Henan, China - Wei Li; Fen Jiao; Xu Wang; Wenfang Che; Zhengquan Zhang; Baijun Xin; Min Xu; Wenqing Qin (Minerals Engineering, 2024)

Regional mangrove vegetation carbon stocks predicted integrating UAV-LiDAR and satellite data - Zongyang Wang; Yuan Zhang; Feilong Li; Wei Gao; Fen Guo; Zhendong Li; Zhifeng Yang (Journal of Environmental Management, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Impact of butylparaben on growth dynamics and microcystin-LR production in Microcystis aeruginosa - Zhong-Hong Zhang; Jian-Wei Zheng; Si-Fen Liu; Ting-Bin Hao; Wei-Dong Yang; Hong-Ye Li; Xiang Wang (Environmental Research, 2024)

Electrochemistry promotion of Fe(Ⅲ)/Fe(Ⅱ) cycle for continuous activation of PAA for sludge disintegration: Performance and mechanism - Jing Zhang; Yanping Zhang; Ning Lv; Fen Li; Yibing Li; Zhenjie Guo (Environmental Research, 2024)

Silk-fibroin-based nanofibrous scaffolds integrated with nano-engineered living bacteria enabling antibiotic-free accelerated infected wound healing - Ming Teng; Xiaomin Luo; Fen Ao; Liuying Li; Jianyan Feng; Peng Zhang; Xiaomeng Zhang; Xudan Liu; Chen Yang; Lufeng Ji; Xuechuan Wang; Haiyan Ju; et al. (Chemical Engineering Journal, 2024)

Superwetting MAX@SiO2 coatings with high photothermal conversion performances for efficient seawater desalination and anti-/de-icing - Helong Zhang; Chuxiong Qiu; Rong Zhang; Hao Zhang; Yunxia Chen; Tao Zeng; Fen Qiao; Lee Li; Ghafar Ali; Xiujian Zhao; Yi Xie (Chemical Engineering Journal, 2024)

Response of periphyton fatty acids to experimental changes in aqueous phosphorus - Bowei Zhou; Yu Wang; Jiaqi You; Feilong Li; Wei Gao; Qingping Du; Yuan Zhang; Fen Guo (Aquatic Ecology, 2024)

Enhancement mechanism for mechanical and water purification performance of piezo-photocatalytic recycled aggregate pervious concrete containing hydrophobic BiOI/BaTiO3 - Guanyu Liu; Hailiang Fei; Jiaxu Zhang; Jiayu Wu; Zhen Feng; Sanqiang Yang; Fen Li; Yuanwen Zhang (Chemical Engineering Journal, 2024)

Converting fruit peels into biodegradable, recyclable and antimicrobial eco-friendly bioplastics for perishable fruit preservation - Shikai Zhang; Xinxin Cheng; Wenjing Yang; Quanbin Fu; Feng Su; Peng Wu; Yijing Li; Fen Wang; Houshen Li; Shiyun Ai (Bioresource Technology, 2024)

Sources and fate of omega-3 polyunsaturated fatty acids in a highly eutrophic lake - Yiduo Luo; Yu Wang; Fen Guo; Martin J. Kainz; Jiaqi You; Feilong Li; Wei Gao; Xiaomei Shen; Juan Tao; Yuan Zhang (Science of The Total Environment, 2024)

Response of weathering carbon sink effect to anthropogenic sulfuric acid in different lithological catchments: A case study from Southwest China - Yincai Xie; Peng Qian; Jun Li; Shi Yu; Xiongyi Miao; Yongli Guo; Fen Huang; Qiong Xiao; Liankai Zhang (Journal of Asian Earth Sciences, 2024)

Effects of different thawing methods on physical and physicochemical properties of frozen dough and quality of corresponding steamed bread - Fan Zhang; Jinying Guo; Peiyao Li; Fen Zhao; Xue Yang; Qiaofen Cheng; J. Stephen Elmore; Ping Wang; Can Cui (Food Chemistry, 2024)

Liquiritin inhibits TGF-β1-induced epithelial mesenchymal transition and extracellular matrix deposition in human renal proximal tubular epithelial cells by suppressing the MAPK signaling - Zhen Chen; Yi jue Liu; Bo Yu; Wei Li; Mengli Zhang; Xian Wu; Feng Gui; Huan Peng; Fen Ai (Molecular & Cellular Toxicology, 2024)

Increasing water nutrient reduces the availability of high-quality food resources for aquatic consumers and consequently simplifies river food webs - Keheng Yan; Fen Guo; Martin J. Kainz; Stuart E. Bunn; Feilong Li; Wei Gao; Xiaoguang Ouyang; Yuan Zhang (Science of The Total Environment, 2024)

Individual and combined treatments of 2,4-epibrassinolide (EBR) and calcium chloride (CaCl2) maintain the postharvest quality of baby mustard - Hongmei Di; Ruobin Liu; Yutong Zhang; Zhifeng Chen; Jie Ma; Victor Hugo Escalona; Duchen Liu; Huanhuan Huang; Zhi Huang; Yi Tang; Huanxiu Li; Bo Sun; et al. (Postharvest Biology and Technology, 2024)

Type and evolution of the Middle Jurassic–Early Cretaceous basin at the northern margin of the Lhasa Block: constraints of sedimentary characteristics and provenance tracing based on zircon U-Pb ages - Fen-Qi Li; Shi-Zhen Zhang; Jun Li; Han Liu; Ya-Dong Qin (Palaeoworld, 2024)

LCQDs modified Bi2MoO6 hydrangea composite photocatalyst for tetracycline degradation from wastewater: Performance, efficiency, and adsorption synergistic photocatalytic mechanism - Dan Xu; Hong Yan; Fen Li; Yuchen Lin; Yuanbo Zhang; Cailian Yu (Journal of Environmental Chemical Engineering, 2024)

Refined building thermal climate zoning scheme in regions with mountainous terrain for accurate building energy-saving potential estimation - Tianyu Zhang; Mingcai Li; Yong Wang; Jie Zhou; Yonghua Li; Fen Zhang; Jingfu Cao; Xianyan Chen; Bao-Jie He (Energy and Buildings, 2024)

China’s mandarin and tangerine cultivation has not reached the carbon emissions peak - Jialiang Liu; Jingyu Zhang; Yingchun Li; Shixiang Zong; Fen Ma; Bohan Zhao (Mitigation and Adaptation Strategies for Global Change, 2024)

Effects of dietary astaxanthin on growth performance, immunity, and tissue composition in largemouth bass, Micropterus salmoides - Jiankun Zhang; Yeshun Yang; Hanying Xu; Xinyu Li; Fen Dong; Qiang Chen; Tao Han; Jiteng Wang; Chenglong Wu (Frontiers in Marine Science, 2024)
This study examined the effects of feeding largemouth bass ( Micropterus salmoides ) with diets containing different doses of astaxanthin (0, 50, 100, 150, and 200 mg/kg) for 8 weeks. The results showed that the values of weight gain significantly increased from 620.32 ± 50.38% to 826.14 ± 33.49% as dietary astaxanthin levels increased from 0 mg/kg to 100 mg/kg. When the astaxanthin level exceeded 150mg/kg, the weight gain rate showed a downward trend, but there was no significant difference among of the 100, 150 and 200 mg/kg groups. The feed conversion ratio (FCR) and protein efficiency ratio (PER) were also improved by adding astaxanthin to diets ( P < 0.05). Meanwhile, adding astaxanthin to the feed increased the length and thickness of intestinal villus and muscle layer thickness ( P < 0.05). The astaxanthin supplementation increased the expression of the NF-E2-related factor ( Nrf2 ) gene and reduced malondialdehyde (MDA) content and the expression of apoptosis genes Caspase-9 and Caspase-3 ( P < 0.05), indicating that it has a good antioxidant ability. Furthermore, adding astaxanthin increased the content of non-specific immune markers and decreased the expression levels of the inflammatory factors interleukin-15 ( IL-15 ) and tumor necrosis factor-α ( TNF-α ). Moreover, fish fed diets with astaxanthin exhibited lower blood cortisol levels ( P < 0.05). The proportions of C20:4n6 (ARA) and C20:5n3 (EPA) in the liver decreased with increasing dietary astaxanthin levels. Based on WGR and SGR values, the optimal addition level of astaxanthin in largemouth bass feed is 134.8 mg/kg ~ 135.75 mg/kg. In summary, the appropriate dietary astaxanthin enhanced the antioxidant capacity and immune response of largemouth bass and had a positive effect on its intestinal health.

Quantitative differentiation of toxicity contributions and predicted global risk of fipronil and its transformation products to aquatic invertebrates - Fen Liu; Huizhen Li; Xiaolei Zhang; Hao Hu; Biyao Yuan; Jing You (Water Research, 2024)

Study on flotation recovery of typical carbon-bearing lead-zinc sulphide ore in Guizhou with pre-decarbonization - Guanghui Li; Zheyi Zhang; Qian Wei; Fen Jiao; Congren Yang; Wei Li; Wenqing Qin (Geochemistry, 2024)

In vitro degradation and dual responsively antibacterial zeolitic imidazolate frameworks-8@Rhein composite coating on magnesium alloy - Chen-Hui Duan; Kui Xue; Lan-Yue Cui; Xue-Wen Jiang; Yan-Yu Zhang; Cheng-Bao Liu; Shuo-Qi Li; Fen Zhang; Rong-Chang Zeng (Chemical Engineering Journal, 2024)

Analysis of blood biochemistry and non-targeted metabolomics of endometritis in dairy cows - Guoshang Ji; Junxing Zhang; Xue Feng; Hui Sheng; Honghong Hu; Fen Li; Yanfen Ma; Yamei Hu; Rina Na; Wenfei Yang; Yun Ma (Animal Reproduction Science, 2024)

The spatial-temporal evolution and driving mechanism of Urban resilience in the Yellow River Basin cities - Haiyang Li; Ying Wang; Hongwei Zhang; Ruimin Yin; Chong Liu; Zhaojun Wang; Fen Fu; Jiaqi Zhao (Journal of Cleaner Production, 2024)

Cotton crop transpiration reveals opportunities to reduce yield loss when applying defoliants for efficient mechanical harvesting - Yongfan Chen; Jochem B. Evers; Mingfeng Yang; Xuejiao Wang; Zeshan Zhang; Shuai Sun; Yutong Zhang; Sen Wang; Fen Ji; Dao Xiang; Jie Li; Chunrong Ji; et al. (Field Crops Research, 2024)

Impact of Cross-Limb Stent-Graft Configuration on Hemodynamics in Abdominal Aortic Aneurysm Interventional Therapy - Yanqing Xie; Yating Zhu; Yike Shi; Yawei Zhao; Hongpeng Zhang; Fen Li; Hui Song; Lingfeng Chen; Wei Guo (Cardiovascular Engineering and Technology, 2024)

Relationship between extreme climate and vegetation in arid and semi-arid mountains in China: A case study of the Qilian Mountains - Lanya Liu; Xiaohua Gou; Xuejia Wang; Meixue Yang; Liya Qie; Guojin Pang; Sihao Wei; Fen Zhang; Yijia Li; Qi Wang; Tao Wang (Agricultural and Forest Meteorology, 2024)

CircHSPB6 Promotes Tumor-Associated Macrophages M2 Polarization and Infiltration to Accelerate Cell Malignant Properties in Lung Adenocarcinoma by CCL2 - Danqing Li; Fan Du; Huiru Jiao; Fen Zhang; Xiaozhen Wang; Shaofeng Zhang (Biochemical Genetics, 2024)

The interleukin enhancer binding factor-2 (ILF2) gene in Penaeus japonicus shrimp: cloning, tissue distribution, and antiviral effects - Junying Xu; Fen Li; Junfeng Zhang; Lin Wang; Xinbo Liu; Wenyu Xue; Yinghua Shi; Yalei Cui (Aquaculture International, 2024)

How do small dams alter river food webs? A food quality perspective along the aquatic food web continuum - Juan Huang; Fen Guo; Michele A. Burford; Martin Kainz; Feilong Li; Wei Gao; Xiaoguang Ouyang; Yuan Zhang (Journal of Environmental Management, 2024)

Geochemical mechanisms of water/CO2-rock interactions in EGS and its impacts on reservoir properties: A review - Binbin Gao; Yiman Li; Zhonghe Pang; Tianming Huang; Yanlong Kong; Bin Li; Fen Zhang (Geothermics, 2024)

Imidacloprid triggered changes in strawberry fruits on edible quality and phenolic profiles by applied at two growth stages - Ning Yue; Chen Zhang; Simeng Li; Hongping Wang; Xiaohui Li; Xueying Chen; Fen Jin (Food Research International, 2024)

Clinical and genetic architecture of a large cohort with auditory neuropathy - Hongyang Wang; Liping Guan; Xiaonan Wu; Jing Guan; Jin Li; Nan Li; Kaili Wu; Ya Gao; Dan Bing; Jianguo Zhang; Lan Lan; Tao Shi; et al. (Human Genetics, 2024)
Auditory neuropathy (AN) is a unique type of language developmental disorder, with no precise rate of genetic contribution that has been deciphered in a large cohort. In a retrospective cohort of 311 patients with AN, pathogenic and likely pathogenic variants of 23 genes were identified in 98 patients (31.5% in 311 patients), and 14 genes were mutated in two or more patients. Among subgroups of patients with AN, the prevalence of pathogenic and likely pathogenic variants was 54.4% and 56.2% in trios and families, while 22.9% in the cases with proband-only; 45.7% and 25.6% in the infant and non-infant group; and 33.7% and 0% in the bilateral and unilateral AN cases. Most of the OTOF gene (96.6%, 28/29) could only be identified in the infant group, while the AIFM1 gene could only be identified in the non-infant group; other genes such as ATP1A3 and OPA1 were identified in both infant and non-infant groups. In conclusion, genes distribution of AN, with the most common genes being OTOF and AIFM1 , is totally different from other sensorineural hearing loss. The subgroups with different onset ages showed different genetic spectrums, so did bilateral and unilateral groups and sporadic and familial or trio groups.

Hydrodynamic cavitation–impinging stream for enhancing ozone mass transfer and oxidation for wastewater treatment - Tao Yang; Lei Zhang; Fen Liu; Chunming Cheng; Guochao Li (Journal of Water Process Engineering, 2024)

Environmental DNA and remote sensing datasets reveal the spatial distribution of aquatic insects in a disturbed subtropical river system - Zongyang Wang; Feilong Li; Feifei Wu; Fen Guo; Wei Gao; Yuan Zhang; Zhifeng Yang (Journal of Environmental Management, 2024)

Elevated atmospheric CO2 promotes the contribution of autotrophic nitrification to N2O emissions in a typical summer maize field - Fen Ma; Yingchun Li; Ying Liu; Libing Dong; Xue Han; Xinyue Zhang; Kuo Li; Liping Guo (European Journal of Agronomy, 2024)

Effect of exposures to multiple metals on blood pressure and hypertension in the elderly: a community-based study - Wen-lei Hu; Wei Xiao; Wen-bin Shen; Yue-yang Wu; Xue Li; Qi Zhong; Guo-ao Li; Huan-huan Lu; Jian-jun Liu; Zhi-hua Zhang; Fen Huang (BioMetals, 2024)

Evaluation and Projection of Extreme High Temperature Indices in Southwestern China Using NEX-GDDP-CMIP6 - Fen Zhang; Linxiao Wei; Yonghua Li; Hongyu Tang; Tianyu Zhang; Baogang Yang (Journal of Meteorological Research, 2024)

Precursor-oriented design of nano-alumina for efficient removal of antibiotics - Hong Guo; Xia-Yin Yin; Li-Fen Zhang; Zheng-Wu Wang; Man-Man Wang; He-Fang Wang (Science of The Total Environment, 2024)

Evidence of strobilurin fungicides and their metabolites in Dongjiang River ecosystem, southern China: Bioaccumulation and ecological risks - Yanan Zhao; Henglin Zhang; Yuxian Liu; Yongyin Lan; Jiamin Zhu; Yanpeng Cai; Fen Guo; Feilong Li; Yuan Zhang; Tao Zhang; Kurunthachalam Kannan; Jingchuan Xue; et al. (Science of The Total Environment, 2024)

Environmental DNA biomonitoring reveals the human impacts on native and non-native fish communities in subtropical river systems - Zhen Li; Feilong Li; Shan Qin; Fen Guo; Shuping Wang; Yuan Zhang (Journal of Environmental Management, 2024)

The effect of the design of the mini cyclonic DPIs on the emitted dose by modelling approach - Zeyu Li; Zhenbo Tong; Lixing Zhang; Fen Huang; Aibing Yu (Journal of Aerosol Science, 2024)

Occurrence and bioaccumulation of parabens and their metabolites in the biota from a subtropical freshwater river ecosystem: Implications for human exposure - Yiling Lin; Yanan Zhao; Yuxian Liu; Yongyin Lan; Jiamin Zhu; Yanpeng Cai; Fen Guo; Feilong Li; Yuan Zhang; Zhihao Xu; Jingchuan Xue (Environmental Research, 2024)

Crocin alleviates neurotoxicity induced by bupivacaine in SH-SY5Y cells with inhibition of PI3K/AKT signaling - Lili Lin; Zhen Chen; Jun Li; Jianye Peng; Jian Wang; Mingjun Feng; Tiancheng Liu; Mengli Zhang; Xian Wu; Fen Ai; Caijie Shen (Genes & Genomics, 2024)

A station-keeping maneuver detection method of non-cooperative geosynchronous satellites - Fen Li; Yufei Zhao; Jingyu Zhang; Ziqiang Zhang; Di Wu (Advances in Space Research, 2024)

Development of a new method framework to estimate the nonlinear and interaction relationship between environmental factors and soil heavy metals - Kaige Lei; Yan Li; Yanbin Zhang; Shiyi Wang; Er Yu; Feng Li; Fen Xiao; Fang Xia (Science of The Total Environment, 2023)

Assessment of the impact of dams on aquatic food webs using stable isotopes: Current progress and future challenges - Fen Guo; Brian Fry; Keheng Yan; Juan Huang; Qian Zhao; Kaitlyn O'Mara; Feilong Li; Wei Gao; Martin J. Kainz; Michael T. Brett; Stuart E. Bunn; Yuan Zhang (Science of The Total Environment, 2023)

Eudesmane-type sesquiterpenoids from the aerial parts of Artemisia lavandulaefolia and their anti-pancreatic cancer activities - Lin-Fen Ding; Guo-Xian Hu; Yu-Yao Liu; Qiu-Hua Wang; Zhang-Juan Li; Meng-Xia Shen; Gui-Fa Zhu; Xing-De Wu; Jia Su (Phytochemistry, 2023)

Three new flavones from the whole plants of Cassia auriculata Linn. and their antiviral activities - Rui-Feng Xiong; Jun-Na Zheng; Qing-Yang Wu; Ning Jiang; Yuan-Sheng He; Yong-Jun Zhang; Ben-Hui Li; Wei Li; Qiu-Fen Hu; Zhen-Yuan Xia; Yin-Ke Li (Phytochemistry Letters, 2023)

Geochemical behaviors of rare earth elements in granite-hosted geothermal systems in SE China - Fen Zhang; Yiman Li; Xiaocheng Zhou; Tianming Huang; Jiao Tian; Yuanzhi Cheng; Yajing Zhao (Geothermics, 2023)

PPAR-γ promotes the polarization of rat retinal microglia to M2 phenotype by regulating the expression of CD200-CD200R1 under hypoxia - Yiyi Hong; Li Jiang; Fen Tang; Mingyuan Zhang; Ling Cui; Haibin Zhong; Fan Xu; Min Li; Changzheng Chen; Lifei Chen (Molecular Biology Reports, 2023)

A single-site porphyrin (Cu)-based COF electrocatalyst for the electrochemical detection of gallic acid sensitively - Mei-Jie Wei; Jing Li; Ze-Qi Wei; Sheng-Feng Zhang; Zhong-Xia Wang; Heng-Ye Li; Rui Zhang; Fen-Ying Kong; Wei Wang (Analytica Chimica Acta, 2023)

Machine learning combined with Geodetector quantifies the synergistic effect of environmental factors on soil heavy metal pollution - Kaige Lei; Yan Li; Yanbin Zhang; Shiyi Wang; Er Yu; Feng Li; Fen Xiao; Zhou Shi; Fang Xia (Environmental Science and Pollution Research, 2023)

Curcumin-mediated photodynamic treatment extends the shelf life of salmon (Salmo salar) sashimi during chilled storage: Comparisons of preservation effects with five natural preservatives - Hui-Ming Chen; Quan Zhou; Li-Jun Huang; Jun Lin; Jia-Fei Liu; Zi-Yong Huang; Rong-Lin Zhang; Jing-Jing Wang; Yong Zhao; Yong-Ning Wu; Xing-Fen Yang; Wei-Liang Wu (Food Research International, 2023)

The impact of multiple metals exposure on the risk of developing proliferative diabetic retinopathy in Anhui, China: a case–control study - Yan-Qing Li; Si-Tian Zhang; Nai-Yu Ke; Yan-Cheng Fang; Wen-Lei Hu; Guo-Ao Li; Fen Huang; Yan-Feng Zhou (Environmental Science and Pollution Research, 2023)

Biofortification of health-promoting glucosinolates in cruciferous sprouts along the whole agro-food chain - Mengyu Wang; Yubo Li; Yuhe Yang; Han Tao; Ghazala Mustafa; Fanliang Meng; Bo Sun; Jiansheng Wang; Yanting Zhao; Fen Zhang; Kejun Cheng; Qiaomei Wang (Trends in Food Science & Technology, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

A new model to accurately measure the radon exhalation rate from soil using AlphaGUARD - Shuaibin Liu; Tao Hu; Fen Lin; Zhongkai Fan; Ruomei Xie; Shuai Yuan; Jiulin Wu; Haibo Yi; Yixiang Mo; Jiale Sun; Linquan Chen; Huiying Li; et al. (Journal of Environmental Radioactivity, 2023)

The Trombe wall equipped with PCMs for the enhancement of the indoor thermal quality - Yuan Zhang; Ziyang Zhu; Zian Peng; Jing Luo; Xiaoqin Sun; Jie Li; Fen Peng (Energy and Buildings, 2023)

Five long-distance dispersals shaped the major intercontinental disjunctions in Tectariaceae s.l. (Polypodiales, Polypodiopsida) - Xia Wan; Liang Zhang; Samuli Lehtonen; Hanna Tuomisto; Da-Wei Zhang; Xin-Fen Gao; Li-Bing Zhang (Molecular Phylogenetics and Evolution, 2023)

Liver-cell protective pyridones from the fungi Tolypocladium album dws120 - Xiao-Qian Wu; Jing Li; Xi Zhou; Jing Wang; Yu-Fen Tan; Ji-Song Mo; Shao Liu; Kang-Ping Xu; Gui-Shan Tan; Wei Zhang; Wen-Xuan Wang (Phytochemistry, 2023)

pH-Regulated lignin as a green catalyst for Highly-Efficient CO2 cycloaddition - Yidan Ouyang; Bin Lei; Zhouqing Tan; Fen Hu; Zhao Wu; Jiaxue Wang; Yixuan Ma; Ran Zhang; Li Guo; Feifei Chen (Fuel, 2023)

CRISPR/Cas9-mediated BoaAOP2s editing alters aliphatic glucosinolate side-chain metabolic flux and increases the glucoraphanin content in Chinese kale - Hao Zheng; Wenli Huang; Xiangxiang Li; Huanhuan Huang; Qiao Yuan; Ruobin Liu; Hongmei Di; Sha Liang; Mengyu Wang; Mengyao Li; Zhi Huang; Yi Tang; et al. (Food Research International, 2023)

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

Three new isoquinoline alkaloids from the cigar tobacco-derived endophytic fungus Aspergillus felis - Yue-Yu Ma; Gui Pu; Xue-Ju Cha; Rui-Feng Xiong; Guang-Hai Zhang; Heng Yao; Mei-Fen Bao; Guang-Hui Kong; Yin-Ke Li; Qiu-Fen Hu; Yu-Ping Wu (Phytochemistry Letters, 2023)

In-situ mechanochemically tailorable 2D gallium oxyselenide for enhanced optoelectronic NO2 gas sensing at room temperature - Tao Tang; Zhong Li; Yin Fen Cheng; Hua Guang Xie; Xuan Xing Wang; Yong Li Chen; Liang Cheng; Yi Liang; Xin Yi Hu; Chu Manh Hung; Nguyen Duc Hoa; Hao Yu; et al. (Journal of Hazardous Materials, 2023)

Metagenomic evidence for antibiotics-driven co-evolution of microbial community, resistome and mobilome in hospital sewage - Jiayu Sun; Yumeng Yuan; Leshan Cai; Mi Zeng; Xin Li; Fen Yao; Weidong Chen; Yuanchun Huang; Muhammad Shafiq; Qingdong Xie; Qiaoxin Zhang; Naikei Wong; et al. (Environmental Pollution, 2023)

Clinical and genome-wide association analysis of chemoradiation-induced hearing loss in nasopharyngeal carcinoma - Yong-Qiao He; Lu-Ting Luo; Tong-Min Wang; Wen-Qiong Xue; Da-Wei Yang; Dan-Hua Li; Hua Diao; Ruo-Wen Xiao; Chang-Mi Deng; Wen-Li Zhang; Ying Liao; Yan-Xia Wu; et al. (Human Genetics, 2023)
Chemoradiation-induced hearing loss (CRIHL) is one of the most devasting side effects for nasopharyngeal carcinoma (NPC) patients, which seriously affects survivors’ long-term quality of life. However, few studies have comprehensively characterized the risk factors for CRIHL. In this study, we found that age at diagnosis, tumor stage, and concurrent cisplatin dose were positively associated with chemoradiation-induced hearing loss. We performed a genome-wide association study (GWAS) in 777 NPC patients and identified rs1050851 (within the exon 2 of NFKBIA ), a variant with a high deleteriousness score, to be significantly associated with hearing loss risk (HR = 5.46, 95% CI 2.93–10.18, P = 9.51 × 10 –08 ). The risk genotype of rs1050851 was associated with higher NFKBIA expression, which was correlated with lower cellular tolerance to cisplatin. According to permutation-based enrichment analysis, the variants mapping to 149 hereditary deafness genes were significantly enriched among GWAS top signals, which indicated the genetic similarity between hereditary deafness and CRIHL. Pathway analysis suggested that synaptic signaling was involved in the development of CRIHL. Additionally, the risk score integrating genetic and clinical factors can predict the risk of hearing loss with a relatively good performance in the test set. Collectively, this study shed new light on the etiology of chemoradiation-induced hearing loss, which facilitates high-risk individuals’ identification for personalized prevention and treatment.

Temporal decline of genetic differentiation among populations of western flower thrips across an invaded range - Li-Na Sun; Li-Jun Cao; Jin-Cui Chen; Li-Jun Ma; Gui-Fen Zhang; San-An Wu; Ary Anthony Hoffmann; Shu-Jun Wei (Biological Invasions, 2023)

Isochromenes from the Nicotiana tabacum -derived endophytic fungus Aspergillus versicolor and their anti-tobacco mosaic virus activities - Feng-Xian Yang; Jia-Meng Dai; Hua-Yin Liu; Qi-Li Mi; Jin Wang; Jian-Duo Zhang; Xue-Mei Li; Wei-Guang Wang; Min Zhou; Yin-Ke Li; Qiu-Fen Hu (Natural Product Research, 2023)

Diterpenes from oriental tobacco Nicotiana tabacum ‘YNOTBS1’ and their bioactivities - Mengjie Peng; Hongmei Zhao; Congqi Zhao; Fen Lv; Guangda Li; Ge Wang; Wenbing Zhou; Zhenjie Li; Zhengxiong Zhao; Ling Zhang; Junju Xu (Natural Product Research, 2023)

Potential translocation process and effects of polystyrene microplastics on strawberry seedlings - Chen Zhang; Ning Yue; Xiaohui Li; Hua Shao; Jing Wang; Lihui An; Fen Jin (Journal of Hazardous Materials, 2023)

Phylogeny, biogeography, and character evolution of the genus Sophora s.l. (Fabaceae, Papilionoideae) - Min Liao; Lara D Shepherd; Jun-Yi Zhang; Yu Feng; Sawai Mattapha; Li-Bing Zhang; Xin-Fen Gao; Bo Xu (Molecular Phylogenetics and Evolution, 2023)

Methimazole and sodium perchlorate exert anti-thyroidal effects in the T3-induced Xenopus laevis metamorphosis assay: A rapid assay for screening thyroid disrupting chemicals - Wei Zhou; Zhan-Fen Qin; Yuan-Yuan Li; Jin-Bo Li; Ya-li Shi; Miao-xin Dong; Xiang Li; Yong-Jun Zhang; Yi-De He (Aquatic Toxicology, 2023)

Production of MSTN knockout porcine cells using adenine base-editing-mediated exon skipping - Shuai-peng Yang; Xiang-xing Zhu; Zi-xiao Qu; Cai-yue Chen; Yao-bing Wu; Yue Wu; Zi-dan Luo; Xin-yi Wang; Chu-yu He; Jia-wen Fang; Ling-qi Wang; Guang-long Hong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2023)

Correlations between flavor and glucosinolates and changes in quality-related physiochemical characteristics of Guizhou suancai during the fermentation process - Hongmei Di; Jie Ma; Yi Zhang; Jia Wei; Jiao Yang; Jun Ma; Jinlin Bian; Jingyi Xu; Zhi Huang; Yi Tang; Huanxiu Li; Yangxia Zheng; et al. (Food Chemistry, 2023)

Sex difference on fibroblast growth factors (FGFs) expression in skin and wound of streptozotocin(STZ)-induced type 1 diabetic mice - Nuo-qi Wang; Wei-hua Jia; Lin Yin; Na Li; Mei-dai Liang; Jia-min Shang; Bi-yu Hou; Li Zhang; Gui-fen Qiang; Guan-hua Du; Xiu-ying Yang (Molecular Biology Reports, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Groundwater recharge mechanisms in a vegetated epikarst spring catchment using water isotopes methods - Yan Deng; Aijun Zhu; Yanqing Li; Fen Yi; Qinjun Zhang; Jing Ke (Carbonates and Evaporites, 2023)

Enhanced production of sugars and UV-shielded lignin/PAN fiber mats from chemi-mechanical pulps - Lei Wang; Xiaohan Li; Chenzhong Wan; Kesheng Zhang; Zhao Wu; Fen Hu; Ran Zhang; Xiao Fu; Hongbo Yu (Science of The Total Environment, 2023)

Maneuverability prediction of the wave glider considering ocean currents - Hongqiang Sang; Zilu Zhang; Xiujun Sun; Shuai Zhang; Can Li; Fen Liu (Ocean Engineering, 2023)

The anti-TMV potency of the tobacco-derived fungus Aspergillus versicolor and its active alkaloids, as anti-TMV activity inhibitors - Jia-Meng Dai; Qi-Li Mi; Xue-Mei Li; Du Gang; Guang-Yu Yang; Jian-Duo Zhang; Jin Wang; Yin-Ke Li; Hai-Ying Yang; Dong Miao; Zhen-Jie Li; Qiu-Fen Hu (Phytochemistry, 2023)

Structural insights into photosynthetic cyclic electron transport - Shumeng Zhang; Baohua Zou; Peng Cao; Xiaodong Su; Fen Xie; Xiaowei Pan; Mei Li (Molecular Plant, 2023)

Molecular mechanisms of glycogen particle assembly in Escherichia coli - Fen Li; Meng-Meng Wang; Qing-Hua Liu; Zhang-Wen Ma; Jun-Jiao Wang; Zi-Yi Wang; Jia-Wei Tang; Jing-Wen Lyu; Zuo-Bin Zhu; Liang Wang (Carbohydrate Polymers, 2023)

Low concentrations of benzophenone-type UV-filters impair testis development in the amphibian Xenopus laevis - Hong-Mei Li; Ying-Chi Zhang; Yuan-Yuan Li; Qing-Qing Zhu; Jie Li; Hai-Ming Xu; Yi-Ming Xiong; Zhan-Fen Qin (Aquatic Toxicology, 2023)

Inhibition of Spinal 5-HT3 Receptor and Spinal Dorsal Horn Neuronal Excitability Alleviates Hyperalgesia in a Rat Model of Parkinson’s Disease - Cheng-Jie Li; Li-Ge Zhang; Lu-Bing Liu; Meng-Qi An; Li-guo Dong; Han-Ying Gu; Yong-Ping Dai; Fen Wang; Cheng-Jie Mao; Chun-Feng Liu (Molecular Neurobiology, 2022)

Association of exposure to multiple serum metals with the risk of chronic kidney disease in the elderly: a population-based case–control study - Wenlei Hu; Guoao Li; Jialiu He; Huanhuan Zhao; Hanshuang Zhang; Huanhuan Lu; Jianjun Liu; Fen Huang (Environmental Science and Pollution Research, 2022)

Short-term exposure to six air pollutants and cause-specific cardiovascular mortality of nine counties or districts in Anhui Province, China - Guoao Li; Huanhuan Zhao; Mingjun Hu; Jialiu He; Wanjun Yang; Hanshuang Zhang; Zhenyu Zhu; Jinliang Zhu; Fen Huang (Environmental Science and Pollution Research, 2022)

Urinary cadmium and peripheral blood telomere length predict the risk of renal function impairment: a study of 547 community residents of Shanxi, China - Jia-Chen Zhang; Shuang-Jing Li; Jian-Yong Guo; Guo-Yan Zhang; Hui Kang; Xiu-Jing Shi; Han Zhou; Yu-Fen Liang; Wei-Tong Shen; Li-Jian Lei (Environmental Science and Pollution Research, 2022)

Identification of Dominant Climate Variables on Spatiotemporal Variation in Reference Evapotranspiration on the Loess Plateau, China - Xiaofei Li; Wei Liang; Lei Jiao; Jianwu Yan; Weibin Zhang; Fengjiao Wang; Fen Gou; Chengxi Wang; Quanqin Shao (Chinese Geographical Science, 2022)

Comparative plastid genome analyses of Rosa: Insights into the phylogeny and gene divergence - Cheng Zhang; Shi-Qi Li; Huan-Huan Xie; Jian-Quan Liu; Xin-Fen Gao (Tree Genetics & Genomes, 2022)

Cavin-1 promotes M2 macrophages/microglia polarization via SOCS3 - Wei Huang; Yiyi Hong; Wenjing He; Li Jiang; Wen Deng; Biyan Peng; Fen Tang; Chaolan Shen; Qianqian Lan; Hui Huang; Haibin Zhong; Jian Lv; et al. (Inflammation Research, 2022)

QTL mapping integrated with BSA-Seq analysis identifies a novel gene conferring resistance to brown planthopper from common wild rice (Oryza rufipogon Griff.) - Xuan Wang; Yue Han; Yue-xiong Zhang; Biao Deng; Bi-qiu Wu; Xin-ying Guo; Yu-fen Qin; Yao-yu Fang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Euphytica, 2022)

Effects of carbon dioxide and green space on sleep quality of the elderly in rural areas of Anhui Province, China - Guoao Li; Zhenyu Zhu; Mingjun Hu; Jialiu He; Wanjun Yang; Jinliang Zhu; Huanhuan Zhao; Hanshuang Zhang; Fen Huang (Environmental Science and Pollution Research, 2022)

Cloning and functional analysis of soluble acid invertase 2 gene (SbSAI-2) in sorghum - Wuyuntanmanda; Fen-Xia Han; Bao-Qing Dun; Ji Zhang; Zhi Wang; Yi Sui; Li Zhu; Gui-Ying Li (Planta, 2022)

Six air pollutants and cause-specific mortality: a multi-area study in nine counties or districts of Anhui Province, China - Guoao Li; Huabing Wu; Qi Zhong; Jialiu He; Wanjun Yang; Jinliang Zhu; Huanhuan Zhao; Hanshuang Zhang; Zhenyu Zhu; Fen Huang (Environmental Science and Pollution Research, 2022)

Adenine base-editing-mediated exon skipping induces gene knockout in cultured pig cells - Xiang-xing Zhu; Jia-sheng Pan; Tao Lin; Ye-cheng Yang; Qiu-yan Huang; Shuai-peng Yang; Zi-xiao Qu; Zi-sheng Lin; Jian-cong Wen; Ai-fen Yan; Juan Feng; Lian Liu; et al. (Biotechnology Letters, 2022)

Exposure to 2,4-dichlorophenol, 2,4,6-trichlorophenol, pentachlorophenol and risk of thyroid cancer: a case-control study in China - Wan-Jun Yang; Hua-Bing Wu; Chi Zhang; Qi Zhong; Ming-Jun Hu; Jia-Liu He; Guo-Ao Li; Zhen-Yu Zhu; Jin-Liang Zhu; Huan-Huan Zhao; Han-Shuang Zhang; Fen Huang (Environmental Science and Pollution Research, 2021)

Comparison on characterization and antioxidant activity of exopolysaccharides from two Porphyridium strains - Wei-Nan Wang; Yi Li; Ying Zhang; Wen-Zhou Xiang; Ai-Fen Li; Tao Li (Journal of Applied Phycology, 2021)

Effects of Melanin Extraction on Biosorption Behavior of Chestnut Shells Towards Methylene Blue - Zhang-Fen Liu; Zhang-Jun Liu; Li-Mei Qie; Zeng-Yu Yao (Water Conservation Science and Engineering, 2021)

Pinocembrin-7-Methylether Protects SH-SY5Y Cells Against 6-Hydroxydopamine-Induced Neurotoxicity via Modulating Nrf2 Induction Through AKT and ERK Pathways - Zhi-Cong Zou; Ji-Jun Fu; Yuan-Ye Dang; Qian Zhang; Xiu-Fen Wang; Han-Bin Chen; Xue-Jing Jia; Simon Ming-Yuen Lee; Chu-Wen Li (Neurotoxicity Research, 2021)

Different posterior hippocampus and default mode network modulation in young APOE ε4 carriers: a functional connectome-informed phenotype longitudinal study - Li Juan Zheng; Li Lin; U. Joseph Schoepf; Akos Varga-Szemes; Rock H. Savage; Han Zhang; Yun Fei Wang; Xin Yuan Zhang; Song Luo; Ya Liu; Gui Fen Yang; Guang Ming Lu; et al. (Molecular Neurobiology, 2021)

Effects of habitat fragmentation on the demography of the critically endangered tree Pterospermum kingtungense (Sterculiaceae) in Yunnan, China - Chun-Ming Yuan; Shan-Shan Zhang; Guo-Ping Yang; Jian Chen; Yun-Fen Geng; Xiao-Shuang Li; Wen-Zhong Yang (Tropical Ecology, 2021)

Effects of Different Component Contents of Colistin Methanesulfonate on the Pharmacokinetics of Prodrug and Formed Colistin in Human - Ya-Xin Fan; Yuan-Cheng Chen; Yi Li; Ji-Cheng Yu; Xing-Chen Bian; Xin Li; Wan-Zhen Li; Bei-Ning Guo; Hai-Lan Wu; Xiao-Fen Liu; Yu Wang; Xiao-Yong Xu; et al. (Pharmaceutical Research, 2021)

Fasudil attenuates glial cell-mediated neuroinflammation via ERK1/2 and AKT signaling pathways after optic nerve crush - Wei Huang; Qianqian Lan; Li Jiang; Wenya Yan; Fen Tang; Chaolan Shen; Hui Huang; Haibin Zhong; Jian Lv; Siming Zeng; Min Li; Zhongxiang Mo; et al. (Molecular Biology Reports, 2020)

Neuronal Activity in the Cerebellum During the Sleep-Wakefulness Transition in Mice - Li-Bin Zhang; Jie Zhang; Meng-Jia Sun; Hao Chen; Jie Yan; Fen-Lan Luo; Zhong-Xiang Yao; Ya-Min Wu; Bo Hu (Neuroscience Bulletin, 2020)

MESP2 variants contribute to conotruncal heart defects by inhibiting cardiac neural crest cell proliferation - Erge Zhang; Jianping Yang; Yang Liu; Nanchao Hong; Huilin Xie; Qihua Fu; Fen Li; Sun Chen; Yu Yu; Kun Sun (Journal of Molecular Medicine, 2020)

Effect of the Interaction Between Cadmium Exposure and CLOCK Gene Polymorphisms on Thyroid Cancer: a Case-Control Study in China - Qian Zhang; Chunxiao Jiang; Haibo Li; Chi Zhang; Huabing Wu; Fen Huang (Biological Trace Element Research, 2020)

Effect of Nitrate Ions on Acidithiobacillus ferrooxidans-Mediated Bio-oxidation of Ferrous Ions and Pyrite - Fen W. Liu; Xing X. Qiao; Ke Xing; Jing Shi; Li X. Zhou; Yan Dong; Wen L. Bi; Jian Zhang (Current Microbiology, 2020)

The expression and role of PIDD in retina after optic nerve crush - Fen Tang; Fan Xu; Ling Cui; Wei Huang; Li Jiang; Lifei Chen; Wenya Yan; Wenjing He; Chaolan Shen; Hui Huang; Jian Lv; Xin Zhao; et al. (Journal of Molecular Histology, 2020)

Molecular and morphological evidence for hybrid origin and matroclinal inheritance of an endangered wild rose, Rosa × pseudobanksiae (Rosaceae) from China - Cheng Zhang; Shi-Qi Li; Yu Zhang; Zhang-Ming Zhu; Jian-Quan Liu; Xin-Fen Gao (Conservation Genetics, 2020)

Controlled Release of Spirotetramat Using Starch–Chitosan–Alginate-Encapsulation - Yan-Li Xie; Wayne Jiang; Fen Li; Yu Zhang; Xiao-Yu Liang; Meng Wang; Xueqing Zhou; Shao-Ying Wu; Cheng-Hui Zhang (Bulletin of Environmental Contamination and Toxicology, 2020)

Phytohalomonas tamaricis gen. nov., sp. nov., an endophytic bacterium isolated from Tamarix ramosissima roots growing in Kumtag desert - Lei Liu; Shi-yan Wang; Cong-fen He; Xiao-xia Zhang; Miao Chi; Li-xiong Liang; Lu-bin Li (Archives of Microbiology, 2020)

Multi‐model analysis of climate impacts on plant photosynthesis in China during 2000–2015 - Hao Yan; Shao‐Qiang Wang; Jun‐Bang Wang; Yun Cao; Ling‐Ling Xu; Men‐Xin Wu; Lu Cheng; Liu‐Xi Mao; Feng‐Hua Zhao; Xian‐Zhou Zhang; Yun‐Fen Liu; Yan‐Fen Wang; et al. (International Journal of Climatology, 2019)
Differences, arising from differences in gross primary production (GPP) model structures and driving forces, have fuelled arguments concerning interannual changes of GPP in China since 2000. To better investigate the interannual variability of GPP and its covariance with climate factors in China, this study adopted a multi‐model analysis based on three GPP models (i.e., Terrestrial Ecosystem Carbon flux model [TEC], Breathing Earth System Simulator model [BESS], and MOD17 GPP model). The results show that annual GPP in China increased by 0.021–0.057 Pg C year −1 from 2000 to 2015 attributable to atmospheric‐CO 2 fertilization effects and favourable climate change, that is, increasing precipitation ( P r ) and temperature ( T a ). However, northern China and southern China had a large difference in the amplitude of these GPP changes; annual GPP increased by 0.017–0.039 Pg C year −1 in northern China but only 0.001–0.018 Pg C year −1 in southern China. Northern China and southern China occupy contrasting climate zones and this contrast produced different interannual variability of GPP through different mechanisms. Northern China has a dry climate with GPP changes sensitive to P r . As a result, more P r along with higher T a in northern China produced the strong uptrend of GPP from 2000 to 2015. In contrast, southern China has a wet climate with its GPP sensitive to solar radiation and T a . For the interval of 2000–2015, decreasing radiation plus drought exerted a negative influence on GPP in southern China. This study highlights the diverse mechanisms in which climate change affects GPP in dry and wet climate zones. A robust multi‐model analysis is preferred to reduce uncertainties arising from a single GPP model and its driving data.

Isolation and synthesis of a new benzylated alkamide from the roots of Lepidium meyenii - Yan-Qing Ye; Zu-Hong Ma; Qiao-Fen Yang; Yan-Qi Sun; Rui-Qi Zhang; Run-Fang Wu; Xin Ren; Li-Juan Mu; Zhi-Yong Jiang; Min Zhou (Natural Product Research, 2019)

A new alkaloid from Portulaca oleracea L. and its antiacetylcholinesterase activity - Fen Xiu; Xuetao Li; Wenjie Zhang; Fan He; Xixiang Ying; Didier Stien (Natural Product Research, 2019)

The analysis of clinical and laboratory data: a large outbreak of dengue fever in Chaozhou, Guangdong province, China - Fen Lin; Hui Yang; Lin Zhang; Sen-Hai Fang; Xiao-Fen Zhan; Li-Ye Yang (Archives of Virology, 2019)

Incidence and clinical correlates of anger attacks in Chinese patients with obsessive-compulsive disorder - Ying-ying Zhang; Heng-fen Gong; Xiao-li Zhang; Wen-juan Liu; Hai-yan Jin; Fang Fang; Sophie Schneider; Elizabeth McIngvale; Chen-cheng Zhang; Wayne K. Goodman; Xi-rong Sun; Eric A. Storch (Journal of Zhejiang University-SCIENCE B, 2019)

Modelling and analysis of net primary productivity and its response mechanism to climate factors in temperate grassland, northern China - Fen Zhao; Bin Xu; Xiuchun Yang; Lang Xia; Yunxiang Jin; Jinya Li; Wenbo Zhang; Jian Guo; Ge Shen (International Journal of Remote Sensing, 2019)

Anti-Hypertensive Action of Fenofibrate via UCP2 Upregulation Mediated by PPAR Activation in Baroreflex Afferent Pathway - Jian Guan; Miao Zhao; Chao He; Xue Li; Ying Li; Jie Sun; Wei Wang; Ya-Li Cui; Qing Zhang; Bai-Yan Li; Guo-Fen Qiao (Neuroscience Bulletin, 2019)

Oral administration of Lactobacillus rhamnosus GG to newborn piglets augments gut barrier function in pre-weaning piglets - Yang Wang; Li Gong; Yan-ping Wu; Zhi-wen Cui; Yong-qiang Wang; Yi Huang; Xiao-ping Zhang; Wei-fen Li (Journal of Zhejiang University-SCIENCE B, 2019)

Phthalate esters in bottled drinking water and their human exposure in Beijing, China - Hui Li; Chunmei Li; Lihui An; Chao Deng; Hang Su; Lufang Wang; Zejun Jiang; Jie Zhou; Jing Wang; Chenghui Zhang; Fen Jin (Food Additives & Contaminants Part B-Surveillance, 2019)

Umbilical Cord Mesenchymal Stem Cells Conditioned Medium Promotes Aβ25-35 phagocytosis by Modulating Autophagy and Aβ-Degrading Enzymes in BV2 Cells - Zhihao Xu; Wenbin Nan; Xiaoyue Zhang; Yuliang Sun; Jichao Yang; Kecheng Lu; Yalin Liu; Yaoxin Gao; Fen Yang; Wenchao Mao; Xuekun Xing; Jiang Du; et al. (Journal of Molecular Neuroscience, 2018)

Transcriptome analysis of Hevea brasiliensis in response to exogenous methyl jasmonate provides novel insights into regulation of jasmonate-elicited rubber biosynthesis - Jin-Ping Liu; Jin Hu; Yan-Hui Liu; Cui-Ping Yang; Yu-Fen Zhuang; Xiu-Li Guo; Yi-Jian Li; Liangsheng Zhang (Physiology and Molecular Biology of Plants, 2018)

Different Hippocampus Functional Connectivity Patterns in Healthy Young Adults with Mutations of APP/Presenilin-1/2 and APOEε4 - Li Juan Zheng; Yun Yan Su; Yun Fei Wang; U. Joseph Schoepf; Akos Varga-Szemes; Jonathan Pannell; Xue Liang; Gang Zheng; Guang Ming Lu; Gui Fen Yang; Long Jiang Zhang (Molecular Neurobiology, 2018)

Minimally Toxic Dose of Lipopolysaccharide and α-Synuclein Oligomer Elicit Synergistic Dopaminergic Neurodegeneration: Role and Mechanism of Microglial NOX2 Activation - Wei Zhang; Jun-hua Gao; Zhao-fen Yan; Xi-yan Huang; Peng Guo; Li Sun; Zhuo Liu; Yang Hu; Li-jun Zuo; Shu-yang Yu; Chen-Jie Cao; Xiao-min Wang; et al. (Molecular Neurobiology, 2018)

Modern greenhouse culture of juvenile soft-shelled turtle, Pelodiscus sinensis - Jing Zhang; Fen Wang; Ye-Lin Jiang; Guan-Jun Hou; Yun-Sheng Cheng; Hong-Lian Chen; Xiang Li (Aquaculture International, 2017)

Repeated Neonatal Sevoflurane Exposure-Induced Developmental Delays of Parvalbumin Interneurons and Cognitive Impairments Are Reversed by Environmental Enrichment - Mu-huo Ji; Zhong-yun Wang; Xiao-ru Sun; Hui Tang; Hui Zhang; Min Jia; Li-li Qiu; Guang-fen Zhang; Yong G. Peng; Jian-jun Yang (Molecular Neurobiology, 2017)

Climate–growth relationships of Schrenk spruce (Picea schrenkiana) along an altitudinal gradient in the western Tianshan mountains, northwest China - Yuxia Huo; Xiaohua Gou; Wenhuo Liu; Jinbao Li; Fen Zhang; Keyan Fang (Trees, 2017)

Interdecadal moisture patterns and teleconnections in Monsoonal Asia over the past seven centuries - Feifei Zhou; Keyan Fang; Fen Zhang; Yingjun Li (International Journal of Climatology, 2017)
Interdecadal (10‐ to 100‐year oscillation) moisture variations over the Monsoonal Asia ( MA ) is highly variable across regions and time, which are relatively less understood due to the shortness of the instrumental data of a few decades. In this study, comprehensive investigations on the spatiotemporal distributions of the interdecadal moisture variations over MA as well as their evolution from prior to the industrial era were conducted utilizing the tree‐ring based drought reconstructions, i.e. the Monsoonal Asia Drought Atlas. Nine interdecadal moisture patterns in MA are identified using the self‐organizing map based on the ensemble empirical mode decomposition. To further investigate these interdecadal moisture patterns, we aggregated the selected nine nodes into four patterns using a hierarchical clustering approach. Among them, Pattern 1 stands for a teleconnection between the Northeast MA and the Indian Peninsula, and Pattern 2 represents a dipole pattern between the Southern and Northern MA . We find that Pattern 1 may be linked with the dynamics of the Antarctic Oscillation that can modulate the strength of the Asian summer monsoon through meridional teleconnections. Pattern 2 is mainly driven by the elevated El Niño‐Southern Oscillation variance and the zonal ‘Silk Road Pattern’ to bridge this interdecadal modulation.

Minocycline ameliorates d-galactose-induced memory deficits and loss of Arc/Arg3.1 expression - Xu Li; Fen Lu; Wei Li; Jun Xu; Xiao-Jing Sun; Ling-Zhi Qin; Qian-Lin Zhang; Yong Yao; Qing-Kai Yu; Xin-Liang Liang (Molecular Biology Reports, 2016)

Gelatin Nanostructured Lipid Carriers Incorporating Nerve Growth Factor Inhibit Endoplasmic Reticulum Stress-Induced Apoptosis and Improve Recovery in Spinal Cord Injury - Si-Pin Zhu; Zhou-Guang Wang; Ying-Zheng Zhao; Jiang Wu; Hong-Xue Shi; Li-Bing Ye; Fen-Zan Wu; Yi Cheng; Hong-Yu Zhang; Songbin He; Xiaojie Wei; Xiao-Bing Fu; et al. (Molecular Neurobiology, 2016)

Rational Improvement of Peptide Affinity to Human Pregnancy-Related Serine Protease HtrA3 PDZ Domain by Introducing a Halogen Bond to the Domain–Peptide Complex Interface - Hong Liu; Shuo-Fen Dou; Xue Zhang; Yan Wang; Qing-Li Wen; Ya-Nan Mu (International Journal of Peptide Research and Therapeutics, 2016)

Genes encoding Δ8-sphingolipid desaturase from various plants: identification, biochemical functions, and evolution - Shu-Fen Li; Guo-Jun Zhang; Xue-Jin Zhang; Jin-Hong Yuan; Chuan-Liang Deng; Zan-Min Hu; Wu-Jun Gao (Journal of Plant Research, 2016)

Repetitive sequences and epigenetic modification: inseparable partners play important roles in the evolution of plant sex chromosomes - Shu-Fen Li; Guo-Jun Zhang; Jin-Hong Yuan; Chuan-Liang Deng; Wu-Jun Gao (Planta, 2016)

Cotton S-adenosylmethionine decarboxylase-mediated spermine biosynthesis is required for salicylic acid- and leucine-correlated signaling in the defense response to Verticillium dahliae - Hui-Juan Mo; Yan-Xiang Sun; Xiao-Li Zhu; Xing-Fen Wang; Yan Zhang; Jun Yang; Gui-Jun Yan; Zhi-Ying Ma (Planta, 2016)

Rapid cloning and bioinformatic analysis of spinach Y chromosome-specific EST sequences - CHUAN-LIANG DENG; WEI-LI ZHANG; YING CAO; SHAO-JING WANG; SHU-FEN LI; WU-JUN GAO; LONG-DOU LU (Journal of Genetics, 2015)

Retraction Note to: Correlations of SELE and SELP genetic polymorphisms with myocardial infarction risk: a meta-analysis and meta-regression - Yu-Juan Zhao; Xia Yang; Li Ren; An-Sheng Cai; Yan-Fen Zhang (Molecular Biology Reports, 2015)

Association between NCF4 rs4821544T/C polymorphism and inflammatory bowel disease risk in Caucasian: a meta-analysis - Peng-Bo Wu; Jin-Fen Dai; Qian Wang; Guo Zhang; Shi-Yun Tan; Ming Li; Hui-Lan Ye (Inflammation Research, 2015)

Modeling the transfer of arsenic from soil to carrot (Daucus carota L.)—a greenhouse and field-based study - Changfeng Ding; Fen Zhou; Xiaogang Li; Taolin Zhang; Xingxiang Wang (Environmental Science and Pollution Research, 2015)

Endoplasmic Reticulum Stress: Relevance and Therapeutics in Central Nervous System Diseases - Hong-Yu Zhang; Zhou-guang Wang; Xiang-Hong Lu; Xiao-Xia Kong; Fen-Zan Wu; Li Lin; Xiaohua Tan; Li-Bing Ye; Jian Xiao (Molecular Neurobiology, 2015)

Orbilia yuanensis sp. nov. and its anamorph - Min Qiao; Jian-Ying Li; Hans-Otto Baral; Ying Zhang; Wen-Yun Qian; Hong-yan Su; Ze-Fen Yu (Mycological Progress, 2015)

Downregulation of Neuregulin 1-ErbB4 Signaling in Parvalbumin Interneurons in the Rat Brain May Contribute to the Antidepressant Properties of Ketamine - Nan Wang; Guang-Fen Zhang; Xiao-Yu Liu; He-Liang Sun; Xing-Ming Wang; Li-Li Qiu; Chun Yang; Jian-Jun Yang (Journal of Molecular Neuroscience, 2014)

Nematodes feel a craving - Using Caenorhabditis elegans as a model to study alcohol addiction - Geng Zhu; Fen Zhang; Wei Li (Neuroscience Bulletin, 2014)

RETRACTED ARTICLE: Correlations of SELE and SELP genetic polymorphisms with myocardial infarction risk: a meta-analysis and meta-regression - Yu-Juan Zhao; Xia Yang; Li Ren; An-Sheng Cai; Yan-Fen Zhang (Molecular Biology Reports, 2014)

Role and Mechanism of Microglial Activation in Iron-Induced Selective and Progressive Dopaminergic Neurodegeneration - Wei Zhang; Zhao-fen Yan; Jun-hua Gao; Li Sun; Xi-yan Huang; Zhuo Liu; Shu-yang Yu; Chen-Jie Cao; Li-jun Zuo; Ze-Jie Chen; Yang Hu; Fang Wang; et al. (Molecular Neurobiology, 2014)

Three homologous genes encoding functional ∆8-sphingolipid desaturase in Populus tomentosa - Shu-Fen Li; Guo-Jun Zhang; Ying-Chun Yuan; Cong-Hui Wang; Wu-Jun Gao; Chuan-Liang Deng; Long-Dou Lu; Zan-Min Hu (Genes & Genomics, 2014)

Uncertainty analysis of downscaling methods in assessing the influence of climate change on hydrology - Fen Ouyang; Haishen Lü; Yonghua Zhu; Jianyun Zhang; Zhongbo Yu; Xi Chen; Min Li (Stochastic Environmental Research and Risk Assessment, 2014)

Identification of the substrate recognition region in the Δ6-fatty acid and Δ8-sphingolipid desaturase by fusion mutagenesis - Li-Ying Song; Yan Zhang; Shu-Fen Li; Jun Hu; Wei-Bo Yin; Yu-Hong Chen; Shan-Ting Hao; Bai-Lin Wang; Richard R.-C. Wang; Zan-Min Hu (Planta, 2014)

Multi-mode PolInSAR experiments using an airborne X-band SAR system in China - Li-Jun Lu; Ji-Xian Zhang; Fen-Fen Hua; Guo-Man Huang (International Journal of Remote Sensing, 2014)

Is there a difference in cognitive development between preschool singletons and twins born after intracytoplasmic sperm injection or in vitro fertilization? - Lan-Feng Xing; Yu-Li Qian; Lu-Ting Chen; Fan-Hong Zhang; Xin-Fen Xu; Fan Qu; Yi-Min Zhu (Journal of Zhejiang University-SCIENCE B, 2014)

The role of sucrose-metabolizing enzymes in pear fruit that differ in sucrose accumulation - Hu Ping Zhang; Ju You Wu; Gai Hua Qin; Gai Fang Yao; Kai Jie Qi; Li Fen Wang; Shao Ling Zhang (Acta Physiologiae Plantarum, 2014)

Responses of CO 2 , N 2 O and CH 4 fluxes between atmosphere and forest soil to changes in multiple environmental conditions - Junhua Yan; Wei Zhang; Keya Wang; Fen Qin; Wantong Wang; Huitang Dai; Peixue Li (Global Change Biology, 2014)
To investigate the effects of multiple environmental conditions on greenhouse gas ( CO 2 , N 2 O , CH 4 ) fluxes, we transferred three soil monoliths from Masson pine forest ( PF ) or coniferous and broadleaved mixed forest ( MF ) at Jigongshan to corresponding forest type at Dinghushan. Greenhouse gas fluxes at the in situ (Jigongshan), transported and ambient (Dinghushan) soil monoliths were measured using static chambers. When the transported soil monoliths experienced the external environmental factors (temperature, precipitation and nitrogen deposition) at Dinghushan, its annual soil CO 2 emissions were 54% in PF and 60% in MF higher than those from the respective in situ treatment. Annual soil N 2 O emissions were 45% in PF and 44% in MF higher than those from the respective in situ treatment. There were no significant differences in annual soil CO 2 or N 2 O emissions between the transported and ambient treatments. However, annual CH 4 uptake by the transported soil monoliths in PF or MF was not significantly different from that at the respective in situ treatment, and was significantly lower than that at the respective ambient treatment. Therefore, external environmental factors were the major drivers of soil CO 2 and N 2 O emissions, while soil was the dominant controller of soil CH 4 uptake. We further tested the results by developing simple empirical models using the observed fluxes of CO 2 and N 2 O from the in situ treatment and found that the empirical models can explain about 90% for CO 2 and 40% for N 2 O of the observed variations at the transported treatment. Results from this study suggest that the different responses of soil CO 2 , N 2 O , CH 4 fluxes to changes in multiple environmental conditions need to be considered in global change study.

Regulation of Autophagy and Ubiquitinated Protein Accumulation by bFGF Promotes Functional Recovery and Neural Protection in a Rat Model of Spinal Cord Injury - Hong-Yu Zhang; Zhou-Guang Wang; Fen-Zan Wu; Xiao-Xia Kong; Jie Yang; Bei-Bei Lin; Shi-Ping Zhu; Li Lin; Chao-Shi Gan; Xiao-Bing Fu; Xiao-Kun Li; Hua-Zi Xu; et al. (Molecular Neurobiology, 2013)

Genetic variation in alkaloid accumulation in leaves of Nicotiana - Bo Sun; Fen Zhang; Guo-jun Zhou; Guo-hai Chu; Fang-fang Huang; Qiao-mei Wang; Li-feng Jin; Fu-cheng Lin; Jun Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Molecular characterization of novel haplotypes of eIF4E family in Chinese cabbage (Brassica rapa L. ssp. pekinensis) - Shuan-Tao Liu; Zhi-Gang Zhang; Qiao-Yun Li; Shu-Fen Wang; Zhi-Zhong Zhao; Jin-Dong Lu; Wen-Ling Xu; Xian-Xian Liu; Wei-Min Fu (Genes & Genomics, 2013)

Effects of perfluorooctanesulfonate and perfluorobutanesulfonate on the growth and sexual development of Xenopus laevis - Qin-Qin Lou; Yin-Feng Zhang; Zhen Zhou; Ya-Li Shi; Ya-Nan Ge; Dong-Kai Ren; Hai-Ming Xu; Ya-Xian Zhao; Wu-Ji Wei; Zhan-Fen Qin (Ecotoxicology, 2013)

Activating transcription factor 4 is involved in endoplasmic reticulum stress-mediated apoptosis contributing to vascular calcification - Xiao-Hui Duan; Jin-Rui Chang; Jing Zhang; Bao-Hong Zhang; Yu-Lin Li; Xu Teng; Yi Zhu; Jie Du; Chao-Shu Tang; Yong-Fen Qi (Apoptosis, 2013)

A Rhodamine-Cyclen Conjugate as Chromogenic and Fluorescent Chemosensor for Copper Ion in Aqueous Media - Min Wang; Di Zhang; Man Li; Min Fan; Yong Ye; Yu-fen Zhao (Journal of Fluorescence, 2013)

Individual and time-varying tree-ring growth to climate sensitivity of Pinus tabuliformis Carr. and Sabina przewalskii Kom. in the eastern Qilian Mountains, China - Fen Zhang; Xiaohua Gou; Wenhuo Liu; D. F. Levia; Yingjun Li (Trees, 2013)

Molecular cloning and functional analysis of a blue light receptor gene MdCRY2 from apple (Malus domestica) - Yuan-Yuan Li; Ke Mao; Cheng Zhao; Xian-Yan Zhao; Rui-Fen Zhang; Hua-Lei Zhang; Huai-Rui Shu; Yu-Jin Hao (Plant Cell Reports, 2013)

Down-regulation of platelet-derived growth factor-D expression blockades NF-κB pathway to inhibit cell proliferation and invasion as well as induce apoptosis in esophageal squamous cell carcinoma - Yu Han; Xiao-He Guo; Qing-Fen Zheng; Yan-Li Zhu; Ying-Ying Fan; Xiu-Ying Zhang (Molecular Biology Reports, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Paroxetine up-regulates neurogenesis in hippocampus-derived neural stem cell from fetal rats - Zheng-wu Peng; Fen Xue; Hua-ning Wang; Rui-guo Zhang; Yun-chun Chen; Ying Wang; Li-yi Zhang; Juan Fan; Qing-rong Tan (Molecular and Cellular Biochemistry, 2013)

Cloning arginine kinase gene and its RNAi in Bursaphelenchus xylophilus causing pine wilt disease - Xin-rong Wang; Xi Cheng; Ya-dong Li; Jin-ai Zhang; Zhi-fen Zhang; Han-rong Wu (European Journal of Plant Pathology, 2012)

Synthesis, properties and application research of atrazine Fe3O4@SiO2 magnetic molecularly imprinted polymer - Hai-Fen Men; Hai-Qing Liu; Zu-Lei Zhang; Jing Huang; Jian Zhang; Yun-Yun Zhai; Lei Li (Environmental Science and Pollution Research, 2012)

VEGF is essential for the growth and migration of human hepatocellular carcinoma cells - Lei Zhang; Jia-Ning Wang; Jun-Ming Tang; Xia Kong; Jian-Ye Yang; Fei Zheng; Ling-Yun Guo; Yong-Zhang Huang; Li Zhang; Lin Tian; Shu-Fen Cao; Chang-Hai Tuo; et al. (Molecular Biology Reports, 2012)

Inhibitor of DNA-binding-1/inhibitor of differentiation-1 (ID-1) is implicated in various aspects of gastric cancer cell biology - Wei Li; Chun-Hua Zhang; Yi-Lin Hong; Jun Li; Yong-Mei Hu; Cui-Fen Zhao (Molecular Biology Reports, 2012)

Inhibition of ROS-activated ERK1/2 pathway contributes to the protection of H2S against chemical hypoxia-induced injury in H9c2 cells - Xiao-Bian Dong; Chun-Tao Yang; Dong-Dan Zheng; Li-Qiu Mo; Xiu-Yu Wang; Ai-Ping Lan; Fen Hu; Pei-Xi Chen; Jian-Qiang Feng; Mei-Fen Zhang; Xin-Xue Liao (Molecular and Cellular Biochemistry, 2012)

Orbilia blumenaviensis and its Arthrobotrys anamorph - Min Qiao; Ying Zhang; Shi-Fu Li; H.-O. Baral; E. Weber; Hong-Yan Su; Jian-Ping Xu; Ke-Qin Zhang; Ze-Fen Yu (Mycological Progress, 2012)

Seasonal variation in population characteristics and management implications for brown rats (Rattus norvegicus) within their native range in Harbin, China - Da-Wei Wang; Lin Cong; Ling-Fen Yue; Bao-Huan Huang; Jian-Xu Zhang; Yu Wang; Ning Li; Xiao-Hui Liu (Journal of Pest Science, 2011)

Implementation of a Fast-Track Clinical Pathway Decreases Postoperative Length of Stay and Hospital Charges for Liver Resection - De-Xin Lin; Xuan Li; Qi-Wen Ye; Fen Lin; Lin-Li Li; Qi-Yu Zhang (Cell Biochemistry and Biophysics, 2011)

Alternative splicing of the antitrypsin gene in the silkworm, Bombyx mori - Hui-fen Liu; Yi-nü Li; Ru Jia; Wei-zheng Cui; Zhi-mei Mu; Zhi-fang Zhang (Molecular Biology Reports, 2011)

Assessing the site-specific impacts of climate change on hydrology, soil erosion and crop yields in the Loess Plateau of China - Zhi Li; Wen-Zhao Liu; Xun-Chang Zhang; Fen-Li Zheng (Climatic Change, 2011)

Tree growth and time-varying climate response along altitudinal transects in central China - Keyan Fang; Xiaohua Gou; Fahu Chen; Jinbao Li; Rosanne D’Arrigo; Edward Cook; Tao Yang; Wenhuo Liu; Fen Zhang (European Journal of Forest Research, 2010)

Actinopolyspora xinjiangensis sp. nov., a novel exteremely halophilic actinomycete isolated from a salt lake in Xinjiang, China - Tong-Wei Guan; Ying Liu; Ke Zhao; Zhan-Fen Xia; Xiao-Ping Zhang; Li-Li Zhang (Antonie van Leeuwenhoek, 2010)

Infliximab treatment in two Chinese patients with psoriatic arthritis - Xi Xie; Jin-wei Chen; Fen Li; Jing Tian; Jie-sheng Gao; David Zhang (Journal of Zhejiang University-SCIENCE B, 2010)

Comparison of reproductive strategies in two externally ovipositing non-pollinating fig wasps - Zhen-Ji Wang; Feng-Ping Zhang; Yan-Qiong Peng; Li-Fen Bai; Da-Rong Yang (Symbiosis, 2010)

Bioturbation of Burrowing Crabs Promotes Sediment Turnover and Carbon and Nitrogen Movements in an Estuarine Salt Marsh - Jin Qing Wang; Xiao Dong Zhang; Li Fen Jiang; Mark D. Bertness; Chang Ming Fang; Jia Kuan Chen; Toshihiko Hara; Bo Li (Ecosystems, 2010)

Frequent occurrence of unreduced gametes in Triticum turgidum–Aegilops tauschii hybrids - Lian-Quan Zhang; Deng-Cai Liu; You-Liang Zheng; Ze-Hong Yan; Shou-Fen Dai; Yun-Fang Li; Qi Jiang; Ya-Qing Ye; Yang Yen (Euphytica, 2010)

Germination of Deyeuxia angustifolia as affected by soil type, burial depth, water depth and oxygen level - Youzhi Li; Canming Zhang; Yonghong Xie; Fen Liu (Mitigation and Adaptation Strategies for Global Change, 2009)

Effects of Lactobacillus buchneri and Lactobacillus plantarum on fermentation, aerobic stability, bacteria diversity and ruminal degradability of alfalfa silage - Tao Zhang; Lei Li; Xiao-fen Wang; Zhao-hai Zeng; Yue-gao Hu; Zong-jun Cui (World Journal of Microbiology and Biotechnology, 2009)

Effects of saltmarsh invasion by Spartina alterniflora on arthropod community structure and diets - Yu-Tong Wu; Cheng-Huan Wang; Xiao-Dong Zhang; Bin Zhao; Li-Fen Jiang; Jia-Kuan Chen; Bo Li (Biological Invasions, 2009)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Cadmium Accumulation in the Edible Parts of Different Cultivars of Radish, Raphanus sativus L., and Carrot, Daucus carota var. sativa, Grown in a Cd-contaminated Soil - Rui-Lun Zheng; Hua-Fen Li; Rong-Feng Jiang; Fu-Suo Zhang (Bulletin of Environmental Contamination and Toxicology, 2008)

Unexpected effect of concomitantly administered curcumin on the pharmacokinetics of talinolol in healthy Chinese volunteers - He Juan; Bernd Terhaag; Zang Cong; Zhang Bi-Kui; Zhu Rong-Hua; Wang Feng; Su Fen-Li; Song Juan; Tang Jing; Peng Wen-Xing (European Journal of Clinical Pharmacology, 2007)

Characterization of a bioflocculant from a newly isolated Vagococcus sp. W31 - Jie Gao; Hua-ying Bao; Ming-xiu Xin; Yuan-xia Liu; Qian Li; Yan-fen Zhang (Journal of Zhejiang University-SCIENCE B, 2006)

The Elp3 subunit of human Elongator complex is functionally similar to its counterpart in yeast - Fen Li; Jun Lu; Qiuju Han; Guoping Zhang; Baiqu Huang (Molecular Genetics and Genomics, 2005)

Dynamics of sandy desertification and its driving forces in western Jilin Province - Fang Li; Yan-fen He; Zhi-ming Liu; Bai Zhang (Chinese Geographical Science, 2004)

Annual Reproductive Behavior of Rhinopithecus roxellana - Ren Bao-Ping; Zhang Shu-Yi; Xia Shu-Zhong; Li Qing-Fen; Liang Bing; Lu Min-Qiang (International Journal of Primatology, 2003)

Quantitative ultrastructure of synapses on functionally identified primary afferent neurons in the cat trigeminal mesencephalic nucleus - Shiho Honma; Masayuki Moritani; Li-Fen Zhang; Lai-Qing Lu; Atsushi Yoshida; Kwabena Appenteng; Yoshio Shigenaga (Experimental Brain Research, 2001)